Encapsulating material for power storage device and power storage device using the same

CN114846676BActive Publication Date: 2026-10-09TOPPAN HOLDINGS INC
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202080090250.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-10
Filing Date
2020-12-17
Publication Date
2026-10-09
Estimated Expiration
2040-12-17

AI Technical Summary

Benefits of technology

[0071] According to this disclosure, in its first to third aspects, it is possible to provide a packaging material for an energy storage device that can ensure excellent lamination strength under both room temperature and high temperature conditions, and also has excellent deep-drawing formability, and an energy storage device using the packaging material for the energy storage device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114846676B_ABST
    Figure CN114846676B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a power storage device packaging material at least sequentially provided with a base material layer, a barrier layer, and a sealant layer, and provided with an adhesive layer between the base material layer and the barrier layer, the adhesive layer containing a polyurethane-based compound composed of a reaction product of at least one or more polyester polyol resins and at least one or more polyfunctional isocyanate compounds, the polyfunctional isocyanate compound containing isocyanurate bodies of isophorone diisocyanate, and the content of isocyanate groups in the isocyanurate bodies of isophorone diisocyanate in the polyfunctional isocyanate compound being 5 to 100 mol% based on the total amount of isocyanate groups contained in the polyfunctional isocyanate compound being 100 mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to encapsulation materials for energy storage devices and energy storage devices using such encapsulation materials. Background Technology

[0002] As energy storage devices, known examples include secondary batteries such as lithium-ion batteries, nickel-metal hydride batteries, and lead-acid batteries, as well as electrochemical capacitors such as double-layer capacitors. Due to the miniaturization of portable devices and space constraints, there is a demand for further miniaturization of energy storage devices, making high-energy-density lithium-ion batteries a focus of attention. Previously, metal cans were used as encapsulation materials for lithium-ion batteries, but multilayer films, which are lightweight, have high heat dissipation, and can be manufactured at low cost, are increasingly being used. Lithium-ion batteries using these multilayer films as encapsulation materials are called laminated lithium-ion batteries. The encapsulation material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) to prevent moisture from seeping into the interior. For example, laminated lithium-ion batteries can be manufactured by cold forming a recess in a portion of the encapsulation material, accommodating the battery contents within the recess, folding the remaining portion of the encapsulation material, and sealing the edges using heat sealing (see, for example, Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2013-101765 Summary of the Invention

[0006] The problem that the invention aims to solve

[0007] However, as the next generation of lithium-ion batteries, energy storage devices known as all-solid-state batteries are under research and development. All-solid-state batteries are characterized by using a solid electrolyte instead of an organic electrolyte. While lithium-ion batteries cannot be used at temperatures above the boiling point of the electrolyte (approximately 80°C), all-solid-state batteries can operate at temperatures exceeding 100°C, and the conductivity of lithium-ions can be improved by operating at high temperatures (e.g., 100–150°C or 100–170°C).

[0008] However, when using multilayer films as encapsulation materials to manufacture laminated all-solid-state batteries, insufficient heat resistance of the encapsulation material can compromise interlayer adhesion at high temperatures, leading to reduced lamination strength and potentially decreased sealing of the all-solid-state battery encapsulation. As shown in Patent Document 1, the encapsulation material may have a structure consisting of a substrate layer, a metal foil layer (barrier layer), and a sealant layer laminated with an adhesive layer. However, at high temperatures, the adhesion between the substrate layer and the metal foil layer is prone to decrease. Furthermore, epoxy-based adhesives are known as heat-resistant adhesives, but the cured epoxy adhesives tend to become brittle, resulting in insufficient deep-drawing formability and lamination strength at room temperature for the encapsulation material.

[0009] This disclosure was made in view of the above-mentioned issues. The first to third objectives are to provide a packaging material for a storage device that can ensure excellent lamination strength under both room temperature and high temperature conditions, and also has excellent deep-drawing formability, and a storage device using the packaging material for the storage device.

[0010] Furthermore, when using the multilayer film described above as the encapsulation material to manufacture a laminated all-solid-state battery, delamination may occur between the layers of the encapsulation material (especially between the substrate layer or sealant layer and the barrier layer) due to insufficient heat resistance of the encapsulation material, thereby making the seal of the all-solid-state battery encapsulation inadequate.

[0011] This disclosure was made in view of the above-mentioned issues, and its fourth objective is to provide an encapsulation material with excellent heat resistance.

[0012] Furthermore, in such all-solid-state batteries, the deeper the recesses formed by cold forming, the more battery contents can be accommodated, thus further increasing the energy density. Therefore, for encapsulation materials composed of multilayer films, sufficient deep-drawing formability is required to form recesses of the desired depth.

[0013] This disclosure was made in view of the above-mentioned issues, and its fifth objective is to provide a packaging material with excellent heat resistance and sufficient deep-drawing formability.

[0014] Methods for solving problems

[0015] To achieve the first objective mentioned above, this disclosure provides an encapsulation material for an energy storage device, which comprises at least a substrate layer, a barrier layer, and a sealant layer in sequence. An adhesive layer is provided between the substrate layer and the barrier layer. The adhesive layer contains a polyurethane-based compound composed of a reaction product of at least one polyester polyol resin and at least one polyfunctional isocyanate compound. The polyfunctional isocyanate compound contains an isocyanurate body of isophorone diisocyanate. Based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from the isocyanurate body of isophorone diisocyanate in the polyfunctional isocyanate compound is 5 to 100 mol%.

[0016] For a cured film (adhesive layer) of an adhesive that uses a multifunctional isocyanate compound containing polyester polyol resin as the main agent and isophorone diisocyanate as the curing agent (hereinafter also referred to as "IPDI-isocyanurate") as the curing agent, due to the large molecular structure of IPDI-isocyanurate, the molecular chain mixing is difficult to loosen even when exposed to high temperatures. Therefore, even at high temperatures, the interlayer adhesion is difficult to decrease, and the lamination strength between the substrate layer with the aforementioned adhesive layer inserted in the middle and the aforementioned barrier layer can be sufficiently ensured. In addition, the toughness of the aforementioned adhesive layer is higher than that of the cured film of epoxy adhesive, thereby obtaining excellent deep-drawing formability and excellent lamination strength at room temperature. Therefore, according to the encapsulation material for energy storage devices of this disclosure having the above-described structure, excellent lamination strength at both room temperature and high temperature can be ensured, while excellent deep-drawing formability can be obtained. In addition, IPDI-isocyanurate has an alicyclic structure but no aromatic ring, so using it as a curing agent in adhesive layers has the following advantages: it is difficult to yellow (poor appearance) even when exposed to high temperature environments for a long time.

[0017] In the encapsulation material for the above-mentioned energy storage device, the ratio of the number of isocyanate groups contained in the above-mentioned polyfunctional isocyanate compound to the number of hydroxyl groups contained in the above-mentioned polyester polyol resin can be 2 to 60.

[0018] Setting the ratio of isocyanate groups to hydroxyl groups (NCO / OH) to 2 or higher can further improve lamination strength at high temperatures. The reason is as follows: When there is a sufficient amount of curing agent compared to the main agent, the curing agents react with each other, generating byproducts such as urea resin and biuret resin. These resins are believed to contain active hydrogen groups that interact with polar groups in each layer, increasing interfacial adhesion and thus improving heat resistance. On the other hand, setting the ratio (NCO / OH) to 60 or lower prevents insufficient curing due to excessive curing agent, thereby further improving lamination strength at both room temperature and high temperatures. Furthermore, with an excessive proportion of curing agent, the ratio of urea resin or biuret resin in the cured film increases, increasing the brittleness of the cured film and potentially reducing its moldability. However, setting the ratio (NCO / OH) to 60 or lower prevents such problems.

[0019] In the aforementioned encapsulation materials for energy storage devices, the polyfunctional isocyanate compound may further contain an adduct of toluene diisocyanate (hereinafter also referred to as "TDI-adduct"). TDI-adduct possesses intermolecular interactions (π-π stacking) or urethane bonds and exhibits excellent cohesiveness. Therefore, although not as good as IPDI-isocyanurate, it still possesses relatively good heat resistance and, at room temperature, demonstrates superior bonding strength and deep-drawing formability compared to IPDI-isocyanurate. Therefore, by using IPDI-isocyanurate and TDI-adduct together, excellent lamination strength at both room temperature and high temperature environments can be ensured with a good balance, and superior deep-drawing formability can be obtained.

[0020] Here, the ratio of the number of isocyanate groups from the isocyanurate body of the aforementioned isophorone diisocyanate to the number of isocyanate groups from the adduct of the aforementioned toluene diisocyanate contained in the aforementioned polyfunctional isocyanate compound can be 0.05 to 20. The ratio of the number of isocyanate groups from IPDI-isocyanurate (NCO) is used to determine the ratio of isocyanate groups to isocyanurate. A The number of isocyanate groups relative to the number of TDI-adducts (NCO) B The ratio of NCO A / NCO B Setting the ratio (NCO) to 0.05 or higher allows for the full realization of the improved heat resistance provided by IPDI-isocyanurate, thus ensuring lamination strength under high-temperature conditions. Furthermore, when the ratio (NCO) is... A / NCO B When the ratio (NCO) is 0.05 or higher, delamination during exposure to high temperatures after deep drawing can be effectively suppressed. On the other hand, by increasing the ratio (NCO)... A / NCOB Setting the value to below 20 allows for full utilization of the improved adhesion at room temperature brought about by TDI-additives, thereby further enhancing lamination strength and deep-drawing formability at room temperature.

[0021] In the aforementioned encapsulation material for energy storage devices, the mass per unit area of ​​the adhesive layer can be 2.0–6.0 g / m². 2 By setting the mass per unit area to 2.0 g / m² 2 The above ensures sufficient adhesive layer thickness, allowing its rigidity to approach that of the substrate and barrier layers. This further improves deep-drawing formability and lamination strength at both room temperature and high temperatures. On the other hand, when the mass per unit area exceeds 6.0 g / m²... 2 At this stage, it is difficult to achieve further improvements in deep-drawing formability and lamination strength. Therefore, from the perspective of suppressing the increase in film thickness and cost, it is preferable to set the mass per unit area to 6.0 g / m². 2 the following.

[0022] In the aforementioned encapsulation material for energy storage devices, an anti-corrosion treatment layer can be provided on one or both surfaces of the barrier layer. By providing the anti-corrosion treatment layer, corrosion of the barrier layer can be prevented, and the adhesion between the barrier layer and its adjacent layers can be improved. Furthermore, in all-solid-state batteries, sulfide-based materials are sometimes used as the electrolyte; however, when moisture penetrates into the encapsulation material, the sulfide compounds react with water to generate hydrogen sulfide (H2S). The adhesion between the barrier layer and its adjacent layers may be reduced due to this H2S. However, when the aforementioned encapsulation material for energy storage devices is used as the encapsulation material for all-solid-state batteries, by providing an anti-corrosion treatment layer on the surface of the barrier layer, the barrier layer can be given resistance to H2S, thereby preventing a reduction in the adhesion between the barrier layer and its adjacent layers.

[0023] In the aforementioned encapsulation material for energy storage devices, the substrate layer can be composed of a polyamide film or a polyester film. Using a polyamide film or a polyester film in the substrate layer can further improve deep-drawing formability. Furthermore, when a polyethylene terephthalate film is used in the substrate layer, the adhesion to the adhesive layer is higher, resulting in further improvements in heat resistance and deep-drawing formability.

[0024] The encapsulation materials used in the above-mentioned energy storage devices can be used in all-solid-state batteries.

[0025] This disclosure also provides an energy storage device comprising: an energy storage device body, a current output terminal extending from the energy storage device body, and the aforementioned encapsulation material for the energy storage device of this disclosure, which clamps the current output terminal and accommodates the energy storage device body. The energy storage device may be an all-solid-state battery.

[0026] To achieve the second objective mentioned above, this disclosure provides an encapsulation material for an energy storage device, characterized in that it is composed of a laminate, the laminate comprising at least sequentially: a substrate layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a sealant layer.

[0027] When the substrate layer is removed to expose the first adhesive layer, and the attenuated total internal reflection of the exposed adhesive layer is measured using Fourier transform infrared spectroscopy from the outermost surface of the exposed adhesive layer, the baseline transmittance T0 at 2100 cm⁻¹ is... -1 Up to 2400cm -1 The minimum transmittance T1 detected within the range, and at 1670 cm⁻¹ -1 Up to 1700cm -1 The minimum transmittance T2 detected within the range satisfies the relationship 0.06≤(T0-T1) / (T0-T2)≤0.4.

[0028] When the relationship 0.06 ≤ (T0-T1) / (T0-T2) ≤ 0.4 is satisfied, the tensile strength and elongation at break of the first adhesive layer are close to the values ​​of each layer (mainly the barrier layer and the substrate), resulting in improved moldability. Furthermore, when molded articles obtained using the encapsulation material of this disclosure are exposed to a high-temperature environment (150°C), the reaction between unreacted curing agents is promoted, thus increasing the Tg of the first adhesive layer and improving its heat resistance.

[0029] In the encapsulation material for the aforementioned energy storage device, the first adhesive layer may contain a polyfunctional isocyanate compound. This polyfunctional isocyanate compound may be composed of at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing aromatic rings in their molecular structure. By specifying the structure of the isocyanate compound as a compound containing alicyclic and benzene rings, initial adhesion and heat resistance can be improved.

[0030] In the encapsulation material for the aforementioned energy storage device, the first adhesive layer may contain a urethane resin, which is formed from at least one polyol selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate diols, and the polyfunctional isocyanate polymer. When the polyol component is selected from polyester polyols, acrylic polyols, and polycarbonate diols (PCD), heat resistance and moldability are improved. Polyester polyols are preferred.

[0031] In the encapsulation material for the aforementioned energy storage device, the ratio of the number of isocyanate groups in the polyfunctional isocyanate polymer to the number of hydroxyl groups in the polyol can be 5 to 60. By setting the NCO / OH ratio to a value within this range, the lamination strength at high temperatures can be improved and the reduction in moldability can be prevented.

[0032] In the encapsulation material for the aforementioned energy storage device, the coating amount of the urethane resin after drying can be 2.0 g / m³. 2 Above 6.0g / m 2 The following applies when the coating amount is less than 2.0 g / m². 2 When the coating thickness is small, stress dispersion decreases, potentially reducing formability. Conversely, increasing the coating amount results in a thicker adhesive layer, improving formability due to enhanced stress dispersion. However, even with a coating amount greater than 6.00 g / m², the adhesive layer remains relatively thick. 2 No significant improvement in moldability was observed, therefore, considering factors such as cost, the upper limit of the coating amount is preferably 6.00 g / m². 2 .

[0033] In the aforementioned encapsulation materials for energy storage devices, the barrier layer can be aluminum foil. It offers an excellent overall balance of barrier properties, tensile strength, and cost.

[0034] In the aforementioned encapsulation material for energy storage devices, the thickness of the barrier layer can be 15–100 μm. It exhibits good formability and can help control costs.

[0035] In the aforementioned encapsulation material for energy storage devices, the barrier layer may have an anti-corrosion treatment layer between the first adhesive layer and the barrier layer, or between the second adhesive layer and the barrier layer, or both. This improves the chemical adhesion to the adhesive layer, thus enhancing its formability. Furthermore, when sulfides are used in the solid electrolyte, corrosion resistance to the generated hydrogen sulfide can be imparted.

[0036] In the aforementioned encapsulation materials for energy storage devices, the substrate can be composed of a polyamide film or a polyester-based film. By using a substrate with excellent toughness and heat resistance, heat resistance and moldability can be improved.

[0037] The encapsulation materials used in the above-mentioned energy storage devices can be used in all-solid-state batteries.

[0038] This disclosure also provides an energy storage device comprising: an energy storage device body, a current output terminal extending from the energy storage device body, and the aforementioned encapsulation material for the energy storage device of this disclosure, which clamps the current output terminal and houses the energy storage device body. The energy storage device may be an all-solid-state battery.

[0039] Furthermore, in order to achieve the third objective mentioned above, this disclosure provides an encapsulation material for an energy storage device, characterized in that it comprises at least a substrate layer, a barrier layer, and a sealant layer in sequence.

[0040] An adhesive layer containing a polyurethane compound and a polyamide-imide resin is provided between the substrate layer and the barrier layer.

[0041] Adhesive layers containing polyurethane compounds exhibit higher toughness than cured epoxy adhesive films, resulting in superior deep-drawing properties and excellent lamination strength at room temperature. However, lamination strength is insufficient, for example, at temperatures above 170°C. Polyurethane compounds composed of the reaction product of polyester polyols and isophorone diisocyanate isocyanurate (IPDI-n) possess relatively excellent heat resistance, but even under these conditions, lamination strength is still insufficient at temperatures above 170°C.

[0042] Polyamide-imide resin has relatively high brittleness and therefore poor toughness, but excellent heat resistance. When mixed with polyurethane compounds to form an adhesive layer, it exhibits sufficient lamination strength even at high temperatures, such as above 170°C, and also provides excellent deep-drawing formability. Furthermore, even after deep drawing, it maintains high lamination strength at high temperatures.

[0043] It should be noted that, in the adhesive layer, when the solid content of the polyamide-imide resin relative to the solid content of the polyurethane compound is set as A% by mass, it is preferable that 1.0% by mass < A. Conversely, when the solid content A of the polyamide-imide resin relative to the solid content of the polyurethane compound is less than 1.0% by mass, the lamination strength at high temperatures may become insufficient. Furthermore, it is preferable that A < 20.0% by mass. Conversely, when the solid content A of the polyamide-imide resin relative to the solid content of the polyurethane compound is 20.0% by mass or more, the deep-drawing formability deteriorates.

[0044] Next, the number-average molecular weight Mn of the polyamide-imide resin is preferably 3000 < Mn < 36000. Conversely, when the number-average molecular weight Mn of the polyamide-imide resin is below 3000, the glass transition temperature and softening temperature of the polyamide-imide resin are low, and the lamination strength at high temperatures may become insufficient. Furthermore, when the number-average molecular weight Mn of the polyamide-imide resin is above 36000, it is difficult to dissolve in solvents, and therefore it is difficult to coat and form an adhesive layer.

[0045] Next, the polyurethane compound can be composed of the reaction product of at least one polyol resin and at least one polyfunctional isocyanate compound. Furthermore, at this time, at least one polyol resin selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate polyols can be used as the polyol resin. When the polyol resin is composed of these polyester polyols, acrylic polyols, or polycarbonate polyols, both the lamination strength and moldability at high temperatures are improved.

[0046] Furthermore, as the aforementioned polyfunctional isocyanate compound, at least one isocyanate polymer selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing aromatic rings in their molecular structure can be used. When the polyfunctional isocyanate compound is composed of these alicyclic isocyanate polymers or isocyanate polymers containing aromatic rings in their molecular structure, both lamination strength and moldability are improved. While the reason is unclear, it is presumed to be due to the following: alicyclic isocyanate polymers have a large molecular structure, making it difficult for the molecular chains to unravel even at high temperatures. Furthermore, it is presumed that in isocyanate polymers containing aromatic rings in their molecular structure, the intermolecular interactions increase cohesion, thereby increasing the heat resistance of the cured film itself and thus increasing lamination strength.

[0047] Next, the ratio (NCO / OH) of the number of isocyanate groups in the polyfunctional isocyanate compound to the number of hydroxyl groups in the polyol resin is preferably 1.5 < NCO / OH < 40.0.

[0048] Heat resistance improves when the number of isocyanate groups in the curing agent (polyfunctional isocyanate compound) of a polyurethane-based compound is sufficiently greater than the number of hydroxyl groups in the main agent (polyol resin) (NCO / OH >> 1.0). In this case, with a sufficient number of NCO groups compared to OH groups, the curing agents react with each other to generate byproducts such as urea resin and biuret resin. It is speculated that these urea resins and biuret resins contain active hydrogen groups, which interact with polar groups at the interfaces, increasing interfacial adhesion and thus improving heat resistance.

[0049] Furthermore, to achieve the fourth objective mentioned above, this disclosure provides an encapsulation material for an energy storage device, which has a laminated structure comprising, in sequence, a substrate layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a sealant layer. At least one of the first and second adhesive layers contains a urea compound as a reaction product of an amine resin and a polyisocyanate compound. In the layer containing the urea compound in the first and second adhesive layers, when a depth of 1680–1720 cm is... -1The infrared absorption spectrum peak intensity was set to A1, 1590–1640 cm⁻¹. -1 When the infrared absorption spectrum peak intensity is set to B1, X1, defined by the following formula (1-A), is 10~99.

[0050] X1={B1 / (A1+B1)}×100…(1-A).

[0051] The encapsulation material used in the aforementioned energy storage device exhibits excellent heat resistance. The inventors believe this effect is achieved for the following reasons: The urea groups in urea compounds possess very high cohesive strength. Furthermore, the urea groups contain active hydrogen within the molecule, thus forming hydrogen bonds between the interface of the bonded objects and this active hydrogen, thereby increasing the interfacial adhesion. Additionally, in this adhesive layer, the 1680–1720 cm⁻¹ of the urethane groups is utilized... -1 The infrared absorption spectrum peak intensity and the 1590–1640 cm⁻¹ peak from the urea group. -1 The X1 value, calculated from the infrared absorption spectrum peak intensity, is above 10, indicating that the urea groups in the urea compound exhibit high cohesiveness. Furthermore, since X1 is below 99, over-curing of the adhesive layer is suppressed, resulting in high adhesion of the adhesive layer. Consequently, the aforementioned encapsulation material for the energy storage device exhibits excellent heat resistance.

[0052] In this disclosure, the isocyanate groups of the polyisocyanate compound can be bonded to a blocking agent. Furthermore, the blocking agent can detach from the isocyanate groups of the polyisocyanate compound at 60–120°C. As a result, the obtained encapsulation material exhibits excellent resistance to molding and curling.

[0053] This disclosure may further include an anti-corrosion treatment layer between at least the second adhesive layer and the barrier layer. This further improves heat resistance.

[0054] In this disclosure, only the second adhesive layer may contain a urea-based compound, while the first adhesive layer and the second adhesive layer contain a urea-based compound. This results in an encapsulation material with excellent heat resistance, and the rigidity of the first adhesive layer is easily mitigated, thus improving deep-drawing formability. Furthermore, by containing only a urea-based compound in the second adhesive layer, corrosion of the barrier layer caused by hydrogen sulfide generated from the battery contents within the encapsulation material can be suppressed.

[0055] In this disclosure, the sealant layer may contain at least one of a polyolefin resin and a polyester resin. Because the sealant layer contains at least one of a polyolefin resin and a polyester resin with a high melting point, the heat resistance is further improved.

[0056] In this disclosure, at least one of the first adhesive layer and the second adhesive layer may contain a hydrogen sulfide adsorbent. Therefore, in the resulting encapsulation material, even when hydrogen sulfide is generated from the energy storage device or when hydrogen sulfide is present on the outside of the encapsulation material, delamination between the barrier layer, the substrate layer, and the sealant layer is difficult to occur, thereby achieving excellent hydrogen sulfide resistance.

[0057] This disclosure can be used in all-solid-state batteries. The encapsulation material of this disclosure has excellent heat resistance, and is therefore suitable for all-solid-state battery applications assumed to be used in high-temperature environments.

[0058] To achieve the fifth objective mentioned above, this disclosure provides an encapsulation material for an energy storage device (hereinafter, sometimes simply referred to as "encapsulation material") having a laminated structure, wherein the laminated structure sequentially comprises a substrate layer, a first adhesive layer, a metal foil layer, a second adhesive layer, and a sealant layer. The first and second adhesive layers contain urethane compounds as reaction products of polyol resins and polyisocyanate compounds. In the first and second adhesive layers, when 2250–2290 cm⁻¹… -1 The infrared absorption spectrum peak intensity was set to A2, 1680–1720 cm⁻¹. -1 When the infrared absorption spectrum peak intensity is set to B2, X2, defined by the following formula (1-B), is 10–90, and the glass transition temperatures of the first and second adhesive layers are 60–80 °C.

[0059] X2={B2 / (A2+B2)}×100…(1-B)

[0060] The encapsulation material for the aforementioned energy storage device exhibits excellent heat resistance and sufficient deep-drawing formability. The inventors believe the reasons for achieving this effect are as follows.

[0061] That is, the urethane groups in urethane compounds possess very high cohesive strength. Furthermore, the urethane groups contain active hydrogen atoms within the molecule, thus forming hydrogen bonds with the interface of the adhesive objects, thereby increasing the interfacial adhesion. Additionally, in the adhesive layer, the 1680–1720 cm⁻¹ of the urethane groups... -1 The infrared absorption spectrum peak intensity and the 2250–2290 cm⁻¹ peak intensity from the isocyanate groups used as raw materials. -1 The X2 value, calculated from the infrared absorption spectrum peak intensity, is above 10. Therefore, the urethane groups of the urethane compounds exhibit high cohesiveness. In addition, since the X2 value is below 90, the over-curing of the adhesive layer is suppressed, resulting in high adhesion of the adhesive layer.

[0062] Furthermore, by setting X2, as defined by the above general formula (1-B), to 10–90 and the glass transition temperature to 60–80°C, the adhesive layer has sufficient cross-linking density, thereby possessing the strength to withstand the shear stress applied during deep drawing. Moreover, by keeping X2 and the glass transition temperature within the aforementioned ranges, the adhesive layer does not become excessively hard, and during deep drawing, it can follow the stretching of the substrate layer and the metal foil layer, thereby suppressing the occurrence of microcracks in the adhesive layer.

[0063] As a result, the encapsulation material, which contains urethane compounds in both the first and second adhesive layers, has an X2 value of 10 to 90, and a glass transition temperature of 60 to 80°C, exhibits excellent heat resistance and sufficient deep-drawing formability.

[0064] In this disclosure, the polyol-based resin can be a polyester polyol-based resin. Compared to other polyol-based resins, polyester polyol-based resins tend to have a large number of esters derived from dicarboxylic acids (polar groups) within the molecule, resulting in high hydrogen bonding strength. This improves the adhesion between the adhesive layer and the substrate layer, sealant layer, and metal foil layer. Consequently, the deep-drawing formability of the resulting encapsulation material becomes more superior.

[0065] This disclosure may further include an anti-corrosion treatment layer between at least the second adhesive layer and the metal foil layer. As a result, the deep-drawing formability of the resulting encapsulation material becomes more excellent, and even under high temperature conditions (e.g., 100–150°C), delamination between the layers of the encapsulation material (especially between the substrate layer or sealant layer and the metal foil layer) is less likely to occur, thereby improving heat resistance.

[0066] In this disclosure, the sealant layer may contain at least one of a polyolefin resin and a polyester resin, and may contain a polyester resin. By containing a polyolefin resin with a high melting point in the sealant layer, the heat resistance of the resulting encapsulation material becomes excellent; by containing a polyester resin with an even higher melting point in the sealant layer, the heat resistance of the resulting encapsulation material becomes even better.

[0067] In this disclosure, the polyisocyanate compound may contain aromatic polyisocyanate compounds or adducts of aromatic polyisocyanate compounds. When these compounds are present in the polyisocyanate compound, intermolecular π-π stacking and π-H interactions between aromatic rings occur, thereby increasing the cohesive strength of the adhesive layer. Therefore, by including aromatic polyisocyanate compounds or their adducts in the polyisocyanate compound, the resulting encapsulation material exhibits excellent heat resistance. Furthermore, the adducts of aromatic polyisocyanate compounds possess intramolecular active hydrogen, thus forming hydrogen bonds between the interface of the adhesive and these active hydrogens, thereby increasing the interfacial adhesion. As a result, the heat resistance of the resulting encapsulation material becomes even more superior.

[0068] In this disclosure, at least the second adhesive layer may contain a hydrogen sulfide adsorbent. Therefore, even when hydrogen sulfide is generated from the energy storage device, delamination between the metal foil layer and the sealant layer is difficult to occur, resulting in excellent hydrogen sulfide resistance of the resulting encapsulation material.

[0069] This disclosure can be used in all-solid-state batteries. The encapsulation material of this disclosure has excellent heat resistance and sufficient deep-drawing formability, and is therefore suitable for all-solid-state batteries in which a recess is formed by cold forming and in which the battery contents are housed.

[0070] Invention Effects

[0071] According to this disclosure, in its first to third aspects, it is possible to provide a packaging material for an energy storage device that can ensure excellent lamination strength under both room temperature and high temperature conditions, and also has excellent deep-drawing formability, and an energy storage device using the packaging material for the energy storage device.

[0072] According to this disclosure, in its fourth aspect, an encapsulation material for an energy storage device with excellent heat resistance can be provided.

[0073] According to this disclosure, in its fifth aspect, an encapsulation material for an energy storage device that has excellent heat resistance and sufficient deep-drawing formability can be provided. Attached Figure Description

[0074] [ Figure 1 [This is a schematic cross-sectional view of an encapsulation material for an energy storage device according to one embodiment of the present disclosure.]

[0075] [ Figure 2 [This is a schematic cross-sectional view of an encapsulation material for an energy storage device according to one embodiment of the present disclosure.]

[0076] [ Figure 3 [This is a perspective view of an energy storage device according to one embodiment of the present disclosure.]

[0077] [ Figure 4[This is a schematic cross-sectional view of an encapsulation material for an energy storage device according to one embodiment of the present disclosure.]

[0078] [ Figure 5 [A diagram illustrating an embossed encapsulation material obtained using an encapsulation material for an energy storage device according to one embodiment of the present disclosure.] Figure 5 (a) is its perspective view. Figure 5 (b) along Figure 5 (a) shows a longitudinal section of the bb line of the embossed packaging material.

[0079] [ Figure 6 [A perspective view showing the process of manufacturing a secondary battery using the encapsulation material for an energy storage device according to one embodiment of the present disclosure.] Figure 6 (a) indicates the state of preparing the encapsulation materials for the energy storage device. Figure 6 (b) indicates the state of the encapsulation materials and battery elements for storage devices that are to be processed into embossed designs. Figure 6 (c) indicates the state after a portion of the encapsulation material of the energy storage device is folded and the ends are melted. Figure 6 (d) indicates the state formed by folding both sides of the folded part upwards. Detailed Implementation

[0080] The preferred embodiments of this disclosure will now be described in detail with appropriate reference to the accompanying drawings. It should be noted that in the drawings, identical or equivalent parts are labeled with the same symbols, and repeated descriptions are omitted. Furthermore, the dimensional ratios in the drawings are not limited to those shown in the illustrations.

[0081] The First Aspect

[0082] The first aspect of this disclosure relates to the encapsulation material for an energy storage device, a method for manufacturing the encapsulation material, and the energy storage device.

[0083] Encapsulation materials for energy storage devices

[0084] Figure 1 A cross-sectional view illustrating one embodiment of the encapsulation material for the energy storage device of this disclosure. (See diagram below.) Figure 1As shown, the encapsulation material (encapsulation material for an energy storage device) 10 of this embodiment is a laminate, which comprises: a substrate layer 11; a first adhesive layer 12a disposed on one surface of the substrate layer 11; a barrier layer 13 disposed on the side of the first adhesive layer 12a opposite to the substrate layer 11 and having first and second anti-corrosion treatment layers 14a and 14b on both sides; a second adhesive layer 12b disposed on the side of the barrier layer 13 opposite to the first adhesive layer 12a; and a sealant layer 16 disposed on the side of the second adhesive layer 12b opposite to the barrier layer 13. Here, the first anti-corrosion treatment layer 14a is disposed on the surface of the barrier layer 13 on the substrate layer 11 side, and the second anti-corrosion treatment layer 14b is disposed on the surface of the barrier layer 13 on the sealant layer 16 side. In the encapsulation material 10, the substrate layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the encapsulation material 10 is used such that the substrate layer 11 faces the outside of the energy storage device and the sealant layer 16 faces the inside of the energy storage device.

[0085] In the encapsulation material 10 of this embodiment, at least one of the first adhesive layer 12a and the second adhesive layer 12b is a layer containing a polyurethane-based compound composed of a reaction product of at least one polyester polyol resin and at least one polyfunctional isocyanate compound. Here, the polyfunctional isocyanate compound contains isocyanurate of isophorone diisocyanate (IPDI-isocyanurate), and based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from IPDI-isocyanurate in the polyfunctional isocyanate compound is 5 to 100 mol%.

[0086] The following is a detailed description of each layer constituting the encapsulation material 10.

[0087] <Substrate Layer 11>

[0088] The substrate layer 11 serves the following functions: imparting heat resistance during the sealing process in the manufacture of energy storage devices and suppressing pinholes during molding and distribution. Particularly for encapsulation materials in large-scale energy storage devices, it can also impart scratch resistance, chemical resistance, and insulation.

[0089] The substrate layer 11 is preferably a layer composed of a resin film formed from an insulating resin. Examples of resin films include stretched or unstretched films such as polyester films, polyamide films, polyimide films, and polypropylene films. The substrate layer 11 can be a single-layer film composed of any one of these resin films, or a laminated film composed of two or more of these resin films.

[0090] Among these, polyester film and polyamide film, more preferably polyester film, are preferred as the substrate layer 11 from the viewpoint of excellent formability. These films are preferably biaxially stretched films. Examples of polyester resins constituting the polyester film include polyethylene terephthalate (PET). Examples of polyamide resins constituting the polyamide film include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6,10, poly(m-phenylene adipamide) (MXD6), nylon 11, nylon 12, etc. Among polyamide films, nylon 6 (ONy) is preferred from the viewpoint of excellent heat resistance, puncture strength, and impact resistance.

[0091] Examples of biaxial stretching methods for biaxial films include successive biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining superior deep-drawing formability, biaxially stretched films are preferably those stretched using the tubular biaxial stretching method.

[0092] Furthermore, the melting peak temperature of the substrate layer 11 is preferably higher than that of the sealant layer 16. When the sealant layer 16 has a multilayer structure, the melting peak temperature of the sealant layer 16 refers to the melting peak temperature of the layer with the highest melting peak temperature. The melting peak temperature of the substrate layer 11 is preferably 290°C or higher, more preferably 290–350°C. Examples of resin films that can be used as the substrate layer 11 and have melting peak temperatures within the above range include: nylon films, PET films, polyamide films, polyimide films, polyphenylene sulfide films (PPS films), etc. Commercially available films can be used as the substrate layer 11, and the substrate layer 11 can be formed by coating (coating and drying of a coating solution). It should be noted that the substrate layer 11 can be a single-layer structure or a multilayer structure, and can be formed by coating a thermosetting resin. Furthermore, the substrate layer 11 may contain various additives, such as flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.

[0093] The peak melting temperature T of the substrate layer 11 11 The peak melting temperature T of sealant layer 16 16 The difference (T) 11 -T 16 The temperature difference is preferably 20°C or higher. By making this temperature difference 20°C or higher, the degradation of the appearance of the encapsulation material 10 caused by heat sealing can be further and sufficiently suppressed.

[0094] The thickness of the substrate layer 11 is preferably 5–50 μm, more preferably 6–40 μm, further preferably 10–30 μm, and particularly preferably 12–30 μm. Since the thickness of the substrate layer 11 is 5 μm or more, it tends to improve the pinhole resistance and insulation of the encapsulation material 10 for the energy storage device. When the thickness of the substrate layer 11 exceeds 50 μm, the total thickness of the encapsulation material 10 for the energy storage device becomes large, and sometimes it is necessary to reduce the battery capacity, which is therefore not preferred.

[0095] <First adhesive layer 12a>

[0096] The first adhesive layer 12a is a layer that bonds the substrate layer 11 and the barrier layer 13 together. In the encapsulation material 10 of this embodiment, the first adhesive layer 12a (hereinafter also referred to as "specific adhesive layer") is a layer containing a polyurethane compound, which is composed of a reaction product of at least one polyester polyol resin and at least one polyfunctional isocyanate compound, wherein the polyfunctional isocyanate compound contains IPDI-isocyanurate, and based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from IPDI-isocyanurate in the polyfunctional isocyanate compound is 5 to 100 mol%.

[0097] In a specific adhesive layer, based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from IPDI-isocyanurate in the polyfunctional isocyanate compound is 5–100 mol%, 25–95 mol%, or 50–75 mol%. By ensuring its content is 5 mol% or more, lamination strength at high temperatures can be ensured, and delamination when exposed to high temperatures after deep drawing can be suppressed. On the other hand, the above content can be 100 mol%, but by using polyfunctional isocyanate compounds other than IPDI-isocyanurate in combination, the above content can be less than 100 mol%. When the above content is 95 mol% or less, the lamination strength and deep drawing performance at room temperature tend to be further improved through the combined effect of other polyfunctional isocyanate compounds.

[0098] In a specific adhesive layer, in addition to IPDI-isocyanurate, the multifunctional isocyanate compound may also include at least one selected from the group consisting of toluene diisocyanate adduct (TDI-adduct), hexamethylene diisocyanate adduct, hexamethylene diisocyanate biuret and isocyanurate bodies, toluene diisocyanate biuret and isocyanurate bodies, diphenylmethane diisocyanate adduct, biuret and isocyanurate bodies, and diphenylmethylene diisocyanate adduct, biuret and isocyanurate bodies, and may also contain TDI-adduct. By using such a multifunctional isocyanate compound in combination with IPDI-isocyanurate, the lamination strength and deep-drawing formability at room temperature can be further improved.

[0099] In the case of polyfunctional isocyanate compounds containing TDI-adducts, the number of isocyanate groups (NCO) from IPDI-isocyanurate is... A The number of isocyanate groups relative to the number of TDI-adducts (NCO) B The ratio of NCO A / NCO B The ratio (NCO) can range from 0.05 to 20. From the perspective of heat resistance, the ratio (NCO) can be... A / NCO B The value can be 0.3–6, 2–4, or even 3. Furthermore, the ratio (NCO) A / NCO B The ratio can be 7 to 20. When the ratio is above 0.05, the lamination strength at high temperatures can be sufficiently ensured, and delamination when exposed to high temperatures after deep drawing can be sufficiently suppressed. When the ratio is below 20, the lamination strength and deep drawing formability at room temperature can be further improved.

[0100] In a specific adhesive layer, the ratio (NCO / OH) of the number of isocyanate groups in the polyfunctional isocyanate compound to the number of hydroxyl groups in the polyester polyol resin can be 2–60, 5–50, or 10–30. When this ratio is 2 or higher, the lamination strength at high temperatures can be further improved. When the ratio is 60 or lower, the lamination strength at both room temperature and high temperatures can be further improved.

[0101] The thickness of the first adhesive layer 12a is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, conformability, and processability, it is preferably 1 to 10 μm, and more preferably 3 to 7 μm.

[0102] When the first adhesive layer 12a is a specific adhesive layer, from the viewpoint of ensuring superior lamination strength at both room temperature and high temperature environments and obtaining superior deep-drawing formability, its mass per unit area can be 2.0 to 6.0 g / m². 2 It can also be 2.5–5.0 g / m³ 2 It can also be 3.0~4.0g / m 2 .

[0103] <Barrier Layer 13>

[0104] The barrier layer 13 has water vapor barrier properties that prevent moisture from entering the interior of the energy storage device. Furthermore, the barrier layer 13 has ductility suitable for deep drawing. For example, various metal foils such as aluminum, stainless steel, and copper, or metal vapor-deposited films, inorganic oxide vapor-deposited films, carbon-containing inorganic oxide vapor-deposited films, and films containing these vapor-deposited films can be used as the barrier layer 13. For example, aluminum vapor-deposited films and inorganic oxide vapor-deposited films can be used. One type can be used alone, or in combination of two or more. From the perspectives of mass (specific gravity), moisture resistance, processability, and cost, metal foil is preferred as the barrier layer 13, and aluminum foil is more preferred.

[0105] From the perspective of imparting the desired ductility during molding, annealed soft aluminum foil is particularly preferred as the aluminum foil. However, to further impart pinhole resistance and ductility during molding, iron-containing aluminum foil is more preferred. The iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass, in 100% by mass aluminum foil. By making the iron content 0.1% by mass or more, a packaging material 10 with better pinhole resistance and ductility can be obtained. By making the iron content 9.0% by mass or less, a packaging material 10 with better flexibility can be obtained. Untreated aluminum foil can be used as the aluminum foil, but to impart electrolyte resistance, degreased aluminum foil is preferred. When degreasing the aluminum foil, it can be degreased on only one side or on both sides.

[0106] The thickness of the barrier layer 13 is not particularly limited, but considering barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, more preferably 15 to 100 μm. When it is thinner than 15 μm, the formability may decrease. In addition, when it is thicker than 100 μm, the gravimetric energy density of the battery tends to decrease, and this leads to an increase in cost.

[0107] <First and second anti-corrosion treatment layers 14a, 14b>

[0108] The first and second anti-corrosion treatment layers 14a and 14b are layers provided on the surface of the barrier layer 13 to prevent corrosion of the metal foil (metal foil layer) or the like constituting the barrier layer 13. Furthermore, the first anti-corrosion treatment layer 14a serves to improve the adhesion between the barrier layer 13 and the first adhesive layer 12a. Similarly, the second anti-corrosion treatment layer 14b serves to improve the adhesion between the barrier layer 13 and the second adhesive layer 12b. The first and second anti-corrosion treatment layers 14a and 14b can be layers of the same composition or layers of different compositions. The first and second anti-corrosion treatment layers 14a and 14b (hereinafter also simply referred to as "anti-corrosion treatment layers 14a and 14b") can be formed, for example, by degreasing treatment, hydrothermal modification treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0109] Degreasing treatments can include acid degreasing and alkali degreasing. Acid degreasing can be achieved by using inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid alone, or by using mixtures thereof. Furthermore, as an acid degreasing agent, especially when aluminum foil is used in the barrier layer 13, using an acid degreasing agent prepared by dissolving a fluorine-containing compound such as sodium difluoride in the aforementioned inorganic acids not only achieves aluminum degreasing but also forms passivated aluminum fluorides, thus improving corrosion resistance. Alkali degreasing can be achieved by using methods such as sodium hydroxide.

[0110] Examples of hydrothermal modification treatments include boehmite treatment, which involves impregnating aluminum foil in boiling water with added triethanolamine.

[0111] Anodizing treatments, for example, include aluminite treatment.

[0112] Chemical conversion treatments can be categorized as impregnation or coating. Examples of impregnation-type chemical conversion treatments include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of mixtures of these. On the other hand, examples of coating-type chemical conversion treatments include methods of applying a corrosion-resistant coating agent to the barrier layer 13.

[0113] In these anti-corrosion treatments, when at least a portion of the anti-corrosion treatment layer is formed by any one of hydrothermal modification treatment, anodizing treatment, or chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment beforehand. It should be noted that when using a metal foil that has been degreased after an annealing process as the barrier layer 13, it is not necessary to perform degreasing treatment again when forming the anti-corrosion treatment layers 14a and 14b.

[0114] Coating agents used for coating-type chemical conversion treatments preferably contain trivalent chromium. Furthermore, the coating agent may also contain at least one polymer selected from the group consisting of cationic and anionic polymers described later.

[0115] Furthermore, in the aforementioned processes, particularly in hydrothermal modification and anodizing, a treatment agent is used to dissolve the surface of the aluminum foil, thereby forming aluminum compounds (boehmite, aluminates) with excellent corrosion resistance. Therefore, the process forms a continuous structure from the barrier layer 13 using aluminum foil to the anti-corrosion treatment layers 14a and 14b, thus encompassing the definition of chemical conversion treatment. On the other hand, as described later, the anti-corrosion treatment layers 14a and 14b can also be formed using a simple coating method not included in the definition of chemical conversion treatment. Examples of such methods include using a sol of rare earth element oxides such as cerium oxide with an average particle size of 100 nm or less as a material that provides corrosion protection against aluminum (corrosion inhibitor effect) and is also environmentally friendly. By using this method, even a general coating method can impart corrosion protection to metal foils such as aluminum foil.

[0116] Sols containing the aforementioned rare earth element oxides can include, for example, sols using various solvents such as aqueous, alcoholic, hydrocarbon, ketone, ester, and ether solvents. Among these, aqueous sols are preferred.

[0117] In the sols of the aforementioned rare earth element oxides, inorganic acids such as nitric acid, hydrochloric acid, and phosphoric acid, or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, and lactic acid are typically used as dispersants and stabilizers to stabilize their dispersion. Among these dispersants and stabilizers, phosphoric acid is particularly desirable, as it can (1) stabilize the dispersion of the sol in the encapsulation material 10; (2) improve the adhesion to the barrier layer 13 by utilizing the aluminum chelating ability of phosphoric acid; and (3) easily undergo dehydration condensation of phosphoric acid even at low temperatures, thereby improving the cohesion of the anti-corrosion treatment layers 14a and 14b (oxide layers), etc.

[0118] Examples of phosphoric acid or its salts include orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, or their alkali metal salts or ammonium salts. For the functional performance of the encapsulation material 10, condensed phosphoric acid such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and hypermetaphosphoric acid, or their alkali metal salts or ammonium salts, are preferred. Furthermore, considering the excellent drying film-forming properties (drying capacity, heat) when using the sol of the aforementioned rare earth element oxides to form the anti-corrosion treatment layers 14a and 14b composed of rare earth element oxides using various coating methods, and their superior dehydration condensation properties at low temperatures, sodium salts are more preferred. Water-soluble salts are preferred as phosphates.

[0119] The mixing ratio of phosphate (or its salt) to rare earth element oxides is preferably 1 to 100 parts by mass relative to 100 parts by mass of rare earth element oxides. If the mixing ratio is 1 part by mass or more relative to 100 parts by mass of rare earth element oxides, the rare earth element oxide sol becomes more stable, thereby improving the function of the encapsulation material 10. The mixing ratio is more preferably 5 parts by mass or more relative to 100 parts by mass of rare earth element oxides. Furthermore, if the mixing ratio is 100 parts by mass or less relative to 100 parts by mass of rare earth element oxides, the function of the rare earth element oxide sol is improved. The mixing ratio is more preferably 50 parts by mass or less relative to 100 parts by mass of rare earth element oxides, and even more preferably 20 parts by mass or less.

[0120] The anti-corrosion treatment layers 14a and 14b formed from the aforementioned rare earth element oxide sol are aggregates of inorganic particles. Therefore, even after the drying and curing process, the cohesiveness of the layers themselves may decrease. Thus, in order to replenish the cohesiveness, the anti-corrosion treatment layers 14a and 14b are preferably composited using anionic or cationic polymers.

[0121] As anionic polymers, polymers containing carboxyl groups can be listed, such as poly(meth)acrylic acid (or its salts), or copolymers copolymerized with poly(meth)acrylic acid as the main component. Copolymer components of such copolymers can be listed as: alkyl methacrylate monomers (as alkyl groups, include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.); (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide (as alkyl groups, include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.), N-alkoxy(meth)acrylamide, N,N-dialkoxy(meth)acrylamide... As alkoxy groups, there are monomers containing amide groups such as methoxy, ethoxy, butoxy, and isobutoxy; N-hydroxymethyl (meth)acrylamide and N-phenyl (meth)acrylamide; hydroxyl groups such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; glycidyl (meth)acrylate and allyl glycidyl ether; silane groups such as (meth)acryloyloxypropyltrimethoxysilane and (meth)acryloyloxypropyltriethoxysilane; and isocyanate groups such as (meth)acryloyloxypropyl isocyanate.

[0122] These anionic polymers enhance the stability of the corrosion-resistant layers 14a and 14b (oxide layers) obtained using rare earth element oxide sols. This is achieved by using acrylic resin components to protect the hard and brittle oxide layer, and by capturing ionic contamination (especially sodium ions) from phosphates contained in the rare earth element oxide sols (cation scavengers). In other words, when the corrosion-resistant layers 14a and 14b obtained using rare earth element oxide sols contain alkali metal ions such as sodium or alkaline earth metal ions, the layers are prone to deterioration starting from the sites containing these ions. Therefore, by using anionic polymers to immobilize sodium ions and other ions contained in the rare earth element oxide sols, the resistance of the corrosion-resistant layers 14a and 14b is improved.

[0123] The corrosion-resistant layers 14a and 14b, formed by combining anionic polymers with rare earth element oxide sols, exhibit the same corrosion resistance as those formed by chromate treatment of aluminum foil. The anionic polymer is preferably a structure formed by crosslinking an essentially water-soluble polyanionic polymer. Examples of crosslinking agents used to form this structure include compounds having isocyanate groups, glycidyl groups, carboxyl groups, and oxazoline groups.

[0124] Examples of compounds having an isocyanate group include: toluene diisocyanate, isophthalic diisocyanate or its hydride, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or its hydride, isophorone diisocyanate, and other diisocyanates; or adducts obtained by reacting these isocyanates with polyols such as trimethylolpropane, biuret bodies obtained by reacting them with water, or isocyanate urea bodies as trimers, and other polyisocyanates; or block polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, etc.

[0125] Examples of compounds containing glycidyl groups include: epoxy compounds formed by reacting diols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol with epichlorohydrin; epoxy compounds formed by reacting polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, and sorbitol with epichlorohydrin; and epoxy compounds formed by reacting dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid with epichlorohydrin.

[0126] Compounds containing a carboxyl group include, for example, various aliphatic or aromatic dicarboxylic acids. Additionally, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid can also be used.

[0127] As compounds containing an oxazoline group, for example, in the case of using low molecular weight compounds having two or more oxazoline units or polymerizable monomers such as isopropenyl oxazoline, compounds copolymerized with acrylic monomers such as (meth)acrylic acid, alkyl (meth)acrylate, and hydroxyalkyl (meth)acrylate can be listed.

[0128] Furthermore, the anionic polymer can be reacted with the silane coupling agent; more specifically, the carboxyl groups of the anionic polymer can selectively react with the functional groups of the silane coupling agent, thereby making the crosslinking point a siloxane bond. In this case, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-isocyanate-propyltriethoxysilane, etc., can be used. Among these, epoxy silanes, amino silanes, and isocyanate-based silanes are particularly preferred considering their reactivity with anionic polymers or their copolymers.

[0129] The crosslinking agent is preferably in the proportion of 1 to 50 parts by mass relative to 100 parts by mass of the anionic polymer, more preferably 10 to 20 parts by mass. If the proportion of the crosslinking agent is 1 part by mass or more relative to 100 parts by mass of the anionic polymer, a crosslinked structure is easily and sufficiently formed. If the proportion of the crosslinking agent is 50 parts by mass or less relative to 100 parts by mass of the anionic polymer, the pot life of the coating solution can be improved.

[0130] The method of crosslinking anionic polymers is not limited to the crosslinking agents mentioned above; it can also be a method of forming ionic crosslinks using titanium or zirconium compounds, etc.

[0131] Examples of cationic polymers include polymers containing amines, such as polyethyleneimine, ionic polymeric complexes composed of polyethyleneimine and polymers containing carboxylic acids, primary amine-grafted acrylic resins formed by grafting a primary amine onto the acrylic acid backbone, polyallylamine or its derivatives, and aminophenol. Examples of polyallylamines include homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, and dimethylallylamine. These amines can be free amines or compounds stabilized by acetic acid or hydrochloric acid. Furthermore, maleic acid, sulfur dioxide, etc., can be used as copolymer components. Additionally, types that impart thermal crosslinking properties by partially methoxylating the primary amine can be used, and aminophenol can also be used. Allylamine or its derivatives are particularly preferred.

[0132] Cationic polymers are preferably used in conjunction with crosslinking agents having functional groups such as carboxyl or glycidyl groups that can react with amines / imines. As crosslinking agents that can be used with cationic polymers, polymers containing carboxylic acids that form ionic polymeric complexes with polyethyleneimine can also be used. Examples include polycarboxylic acids (salts) such as polyacrylic acid or its ionic salts, copolymers in which comonomers are introduced, and polysaccharides containing carboxyl groups such as carboxymethyl cellulose or its ionic salts.

[0133] From the perspective of improving adhesion, cationic polymers are a more preferred material. Furthermore, like the anionic polymers described above, cationic polymers are also water-soluble and can form cross-linked structures to impart water resistance, thus making them even more preferred. The cross-linking agent used to form the cross-linked structure in the cationic polymer can be any cross-linking agent described in the section on anionic polymers. When rare earth element oxide sols are used as anti-corrosion treatment layers 14a and 14b, cationic polymers can also be used instead of the aforementioned anionic polymers as their protective layer.

[0134] In corrosion-resistant coatings using chemical conversion treatments, such as chromate treatment, a chemical conversion agent consisting of a mixture of hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, or their salts is used to treat the aluminum foil in order to form an inclined structure with the aluminum foil. Then, chromium or non-chromium compounds react to form a chemical conversion layer on the aluminum foil. However, in the aforementioned chemical conversion treatment, the use of acid in the chemical conversion agent leads to a deterioration of the working environment and corrosion of the coating apparatus. On the other hand, the coating-type corrosion-resistant coatings 14a and 14b, unlike chemical conversion treatments such as chromate treatment, do not require an inclined structure to be formed on the barrier layer 13 using the aluminum foil. Therefore, the properties of the coating agent are not limited by acidity, alkalinity, neutrality, etc., and a good working environment can be achieved. Furthermore, considering the need for alternatives to chromate treatments that use chromium compounds in environmental hygiene, the coating-type corrosion-resistant coatings 14a and 14b are also preferred.

[0135] Based on the above, examples of combinations of the above-mentioned coating-type anti-corrosion treatments can be listed as follows: (1) only rare earth element oxide sol; (2) only anionic polymer; (3) only cationic polymer; (4) rare earth element oxide sol + anionic polymer (layered composite); (5) rare earth element oxide sol + cationic polymer (layered composite); (6) (rare earth element oxide sol + anionic polymer: layered composite) / cationic polymer (multilayered); (7) (rare earth element oxide sol + cationic polymer: layered composite) / anionic polymer (multilayered), etc. Among these, (1) and (4) to (7) are preferred, and (4) to (7) are particularly preferred. However, this embodiment is not limited to the above combinations. For example, as an example of an anti-corrosion treatment option, cationic polymers are a highly preferred material from the perspective of good adhesion between the modified polyolefin resins listed in the description of the adhesive resin layer described later. Therefore, it is possible to design that, in the case where the adhesive resin layer is composed of a modified polyolefin resin, a cationic polymer is provided on the surface in contact with the adhesive resin layer (e.g., the configuration of (5) and (6) etc).

[0136] Furthermore, the anti-corrosion treatment layers 14a and 14b are not limited to the layers described above. For example, they can be formed using a treatment agent that mixes phosphoric acid and chromium compounds into a resin binder (such as aminophenol), as is known in coating-type chromates. If this treatment agent is used, a layer that combines both anti-corrosion and adhesion properties can be formed. Furthermore, although the stability of the coating solution needs to be considered, a coating agent that is pre-liquefied from rare earth element oxide sol and a polycationic polymer or a polyanionic polymer can be used to achieve a layer that combines both anti-corrosion and adhesion properties.

[0137] Regardless of whether it is a multi-layer or single-layer structure, the preferred mass per unit area of ​​the anti-corrosion treatment layers 14a and 14b is 0.005–0.200 g / m². 2 More preferably, it is 0.010–0.100 g / m 2 If the mass per unit area is 0.005 g / m² 2 The above methods easily impart anti-corrosion properties to the barrier layer 13. Furthermore, even if the mass per unit area exceeds 0.200 g / m²... 2 The anti-corrosion function remains largely unchanged. On the other hand, when using rare earth element oxide sols, if the coating is thick, insufficient curing due to heat during drying may lead to reduced cohesion. It should be noted that the thickness of anti-corrosion treatment layers 14a and 14b can be calculated based on their specific gravity.

[0138] From the viewpoint of easily maintaining the tightness between the sealant layer and the barrier layer, the anti-corrosion treatment layers 14a and 14b can be, for example, containing cerium oxide, phosphoric acid or phosphate in a mass ratio of 1 to 100 parts by mass relative to 100 parts by mass of the cerium oxide, and a cationic polymer; they can also be formed by performing a chemical conversion treatment on the barrier layer 13; or they can be formed by performing a chemical conversion treatment on the barrier layer 13 and containing a cationic polymer.

[0139] <Second adhesive layer 12b>

[0140] The second adhesive layer 12b is a layer that bonds the barrier layer 13, to which the second anti-corrosion treatment layer 14b is formed, to the sealant layer 16. In the second adhesive layer 12b, a conventional adhesive used for bonding the barrier layer and the sealant layer can be used. Specifically, materials constituting the second adhesive layer 12b can include, for example, polyurethane resins obtained by interacting a difunctional or more isocyanate compound with a main agent such as a polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol.

[0141] Depending on the required functions and properties of the encapsulation material, the above-mentioned polyols can be used alone or in combination of two or more.

[0142] In addition, various other additives and stabilizers can be mixed into the polyurethane resin described above, depending on the required properties of the adhesive.

[0143] In the encapsulation material 10 of this embodiment, the second adhesive layer 12b may be the specific adhesive layer described above.

[0144] The thickness of the second adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength and processability, it is preferably 1 to 10 μm, more preferably 3 to 7 μm.

[0145] When the second adhesive layer 12b is a specific adhesive layer, from the viewpoint of ensuring superior lamination strength at both room temperature and high temperature environments, and obtaining superior deep-drawing formability, its mass per unit area can be 2.0 to 6.0 g / m². 2 It can also be 2.5–5.0 g / m³ 2 It can also be 3.5–4.5 g / m³ 2 .

[0146] <Sealant Layer 16>

[0147] The sealant layer 16 is a layer that imparts a sealing property to the encapsulation material 10 through heat sealing. Examples of sealant layers 16 include resin films composed of polyolefin or polyester resins. These resins constituting the sealant layer 16 (hereinafter also referred to as "base resins") may be used alone or in combination of two or more.

[0148] Examples of polyolefin resins include: low-density, medium-density, or high-density polyethylene; ethylene-α-olefin copolymers; polypropylene; block or random copolymers containing propylene as a copolymer component; and propylene-α-olefin copolymers, etc.

[0149] Examples of polyester resins include: polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and polypropylene terephthalate (PTT) resin.

[0150] The sealant layer 16 may contain a polyolefin elastomer. The polyolefin elastomer may or may not be compatible with the base resin, but it may contain both compatible and incompatible polyolefin elastomers. Compatible (compatible) means dispersed in the base resin with a dispersed phase size of 1 nm or more and less than 500 nm. Incompatible (incompatible) means dispersed in the base resin with a dispersed phase size of 500 nm or more and less than 20 μm.

[0151] When the base resin is a polypropylene-based resin, examples of compatible polyolefin elastomers include propylene-butene-1 random copolymers, while examples of incompatible polyolefin elastomers include ethylene-butene-1 random copolymers. Polyolefin elastomers can be used alone or in combination of two or more types.

[0152] Furthermore, the sealant layer 16 may contain additives such as slip agents, anti-blocking agents, antioxidants, light stabilizers, and flame retardants. When the total mass of the sealant layer 16 is set to 100 parts by mass, the content of these additives is preferably 5 parts by mass or less.

[0153] The thickness of the sealant layer 16 is not particularly limited, but from the viewpoint of balancing thin film formation and improving heat sealing strength under high temperature conditions, it is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 100 μm, and even more preferably in the range of 20 to 80 μm.

[0154] The sealant layer 16 can be either a single-layer film or a multi-layer film, depending on the required function.

[0155] The preferred embodiment of the encapsulation material for the energy storage device has been described in detail above. However, this disclosure is not limited to this specific embodiment, and various modifications and changes can be made within the scope of the spirit of this disclosure as set forth in the claims.

[0156] For example, Figure 1 The diagram shows a case where anti-corrosion treatment layers 14a and 14b are provided on both sides of the barrier layer 13, but only one of the anti-corrosion treatment layers 14a and 14b may be provided, or no anti-corrosion treatment layer may be provided.

[0157] Figure 1 The diagram shows a case where the barrier layer 13 and the sealant layer 16 are laminated together using the second adhesive layer 12b, but as... Figure 2 As with the encapsulation material 20 used in the energy storage device shown, the barrier layer 13 and the sealant layer 16 can also be laminated together using an adhesive resin layer 15. Furthermore, in Figure 2 In the encapsulation material 20 for the energy storage device shown, a second adhesive layer 12b may be provided between the barrier layer 13 and the adhesive resin layer 15.

[0158] <Adhesive resin layer 15>

[0159] The adhesive resin layer 15 is generally composed of an adhesive resin composition as the main component and additive components added as needed. There are no particular limitations on the adhesive resin composition, but it is preferable to contain a modified polyolefin resin.

[0160] The modified polyolefin resin is preferably a polyolefin resin obtained by graft modification using unsaturated carboxylic acids and unsaturated carboxylic acid derivatives derived from either their anhydrides or esters.

[0161] Examples of polyolefin resins include: low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-α-olefin copolymer, homopolymer polypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0162] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "ADMER" manufactured by Mitsui Chemicals Co., Ltd. and "MODIC" manufactured by Mitsubishi Chemical Corporation are suitable modified polyolefin resins. Such modified polyolefin resins exhibit excellent reactivity with various metals and polymers having various functional groups; therefore, this reactivity can be used to impart adhesion to the adhesive resin layer 15 and improve electrolyte resistance. Furthermore, as needed, the adhesive resin layer 15 may contain various additives such as compatible and incompatible elastomers, flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, and tackifiers.

[0163] There is no particular limitation on the thickness of the adhesive resin layer 15, but from the viewpoint of stress relief and moisture / electrolyte penetration, it is preferable to have the same thickness as or less than that of the sealant layer 16.

[0164] Furthermore, in the encapsulation material 20 for the energy storage device, from the viewpoint of balancing thin-film properties and improving heat-sealing strength under high-temperature conditions, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm.

[0165] [Manufacturing methods for encapsulation materials]

[0166] Next, for Figure 1 An example of a method for manufacturing the encapsulation material 10 will be described. It should be noted that the method for manufacturing the encapsulation material 10 is not limited to the following method.

[0167] The manufacturing method of the encapsulation material 10 in this embodiment generally includes: a step of providing anti-corrosion treatment layers 14a and 14b on the barrier layer 13; a step of bonding the substrate layer 11 and the barrier layer 13 together using a first adhesive layer 12a; a step of further laminating a sealant layer 16 via a second adhesive layer 12b to form a laminate; and a step of aging the resulting laminate as needed.

[0168] (Laying process of anti-corrosion treatment layers 14a and 14b onto barrier layer 13)

[0169] This process involves forming anti-corrosion treatment layers 14a and 14b on the barrier layer 13. As described above, methods for this process include: degreasing the barrier layer 13, hydrothermal modification, anodizing, chemical conversion, or applying a coating agent with anti-corrosion properties.

[0170] Furthermore, when the anti-corrosion treatment layers 14a and 14b are multi-layered, for example, the coating liquid (coating agent) constituting the lower layer side (barrier layer 13 side) of the anti-corrosion treatment layer can be applied to the barrier layer 13 and fired to form a first layer, and then the coating liquid (coating agent) constituting the upper layer side of the anti-corrosion treatment layer can be applied to the first layer and fired to form a second layer.

[0171] Degreasing can be performed using spraying or immersion methods. Hydrothermal modification or anodizing can be performed using immersion methods. For chemical conversion treatments, depending on the type of chemical conversion treatment, immersion, spraying, coating, etc., can be appropriately selected and implemented.

[0172] Regarding the coating methods for anti-corrosion coating agents, various methods can be used, such as gravure coating, reverse coating, roller coating, and bar coating.

[0173] As described above, various treatments can be performed on either side or one side of the metal foil, but in the case of single-sided treatment, it is preferable to perform the treatment on one side of the laminated sealant layer 16. It should be noted that, if necessary, the surface of the substrate layer 11 may also be treated as described above.

[0174] Furthermore, the coating amount of the coating agent used to form both the first and second layers is preferably 0.005 to 0.200 g / m². 2 More preferably, it is 0.010–0.100 g / m 2 .

[0175] Furthermore, when drying and curing are required, the process can be carried out within the range of 60 to 300°C, depending on the drying conditions of the anti-corrosion treatment layers 14a and 14b used.

[0176] (The bonding process between the substrate layer 11 and the barrier layer 13)

[0177] This process involves bonding the barrier layer 13, which has anti-corrosion treatment layers 14a and 14b, to the substrate layer 11 via the first adhesive layer 12a. As a bonding method, dry lamination, solvent-free lamination, wet lamination, or other methods can be used, utilizing the material constituting the first adhesive layer 12a to bond the two together. The drying coating amount of the first adhesive layer 12a is set to 1–10 g / m². 2Within the range, more preferably 2 to 6 g / m 2 Within the range.

[0178] (Laying process of the second adhesive layer 12b and the sealant layer 16)

[0179] This process involves bonding the sealant layer 16 to one side of the second anti-corrosion treatment layer 14b of the barrier layer 13 via the second adhesive layer 12b. Examples of bonding methods include wet lamination and dry lamination.

[0180] In the case of wet processing, a solution or dispersion of the adhesive constituting the second adhesive layer 12b is applied to the second anti-corrosion treatment layer 14b, and the solvent is removed at a predetermined temperature to dry into a film, or, if necessary, a firing process is performed after drying. Then, the sealant layer 16 is laminated to manufacture the encapsulation material 10. Various coating methods exemplified in the previous examples can be listed as coating methods. Preferably, the amount of the second adhesive layer 12b after drying is the same as that of the first adhesive layer 12a.

[0181] In this case, the sealant layer 16 can be manufactured, for example, by using a sealant layer forming resin composition containing the components of the sealant layer 16 described above, and by using a melt extrusion molding machine. From a production point of view, the processing speed of the melt extrusion molding machine can be set to 80 m / min or more.

[0182] (Aging process)

[0183] This process involves aging (curing) the laminate. Aging the laminate promotes adhesion between the barrier layer 13, the second anti-corrosion layer 14b, the second adhesive layer 12b, and the sealant layer 16. The aging process can be performed within the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.

[0184] In this way, it is possible to manufacture such as Figure 1 The encapsulation material 10 shown in this embodiment.

[0185] Next, for Figure 2 An example of a method for manufacturing the encapsulation material 20 will be described. It should be noted that the method for manufacturing the encapsulation material 20 is not limited to the following method.

[0186] The manufacturing method of the encapsulation material 20 in this embodiment generally includes: a step of providing anti-corrosion treatment layers 14a and 14b on the barrier layer 13; a step of bonding the substrate layer 11 to the barrier layer 13 using a first adhesive layer 12a; a step of further laminating an adhesive resin layer 15 and a sealant layer 16 to form a laminate; and a step of heat-treating the resulting laminate as needed. It should be noted that the steps up to bonding the substrate layer 11 to the barrier layer 13 can be performed in the same manner as the manufacturing method of the encapsulation material 10 described above.

[0187] (Lamination process of adhesive resin layer 15 and sealant layer 16)

[0188] This process involves forming an adhesive resin layer 15 and a sealant layer 16 on the second anti-corrosion treatment layer 14b formed in the previous process. One method for this is sandwich lamination of the adhesive resin layer 15 and the sealant layer 16 together using an extrusion laminator. Alternatively, the adhesive resin layer 15 and the sealant layer 16 can be laminated using a duplex extrusion lamination method or a co-extrusion method. In forming the adhesive resin layer 15 and the sealant layer 16, the components can be mixed, for example, in a manner that satisfies the aforementioned composition of the adhesive resin layer 15 and the sealant layer 16. In forming the sealant layer 16, the aforementioned sealant layer forming resin composition can be used.

[0189] Through this process, the following can be obtained: Figure 2 The laminate shown is composed of a substrate layer 11, a first adhesive layer 12a, a first anti-corrosion treatment layer 14a, a barrier layer 13, a second anti-corrosion treatment layer 14b, an adhesive resin layer 15, and a sealant layer 16 stacked sequentially.

[0190] It should be noted that the adhesive resin layer 15 can be directly extruded and laminated with the dried and mixed material using an extrusion laminator to form the above-mentioned material mixture. Alternatively, it can be pre-melted and mixed using a melt kneading device such as a single-shaft extruder, a twin-shaft extruder, or a Brabender mixer, then granulated, and extruded and laminated using an extrusion laminator.

[0191] The sealant layer 16 can be directly extruded and laminated using an extrusion laminator to form a mixture of the aforementioned materials that constitute the resin composition for forming the sealant layer. Alternatively, it can be pre-melted and granulated using a melt-kneading device such as a uniaxial extruder, biaxial extruder, or Brabender mixer. The granules can then be used to laminate the adhesive resin layer 15 and the sealant layer 16 using a biaxial extrusion lamination method or a co-extrusion method. Furthermore, a sealant monolayer can be pre-prepared as a casting film using the sealant layer forming resin composition, and then laminated together with the adhesive resin using a sandwich lamination method. From a production point of view, the forming speed (processing speed) of the adhesive resin layer 5 and the sealant layer 16 can be, for example, 80 m / min or more.

[0192] (Heat treatment process)

[0193] This process involves heat-treating the laminate. By heat-treating the laminate, the adhesion between the barrier layer 13, the second anti-corrosion treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16 can be improved. Preferably, the heat treatment is performed at a temperature at least above the melting point of the adhesive resin layer 15.

[0194] In this way, it is possible to manufacture such as Figure 2 The encapsulation material 20 shown in this embodiment.

[0195] The preferred embodiments of the encapsulation material for the energy storage device disclosed herein have been described in detail above. However, this disclosure is not limited to these specific embodiments, but various modifications and alterations can be made within the scope of the spirit of this disclosure as set forth in the claims.

[0196] The encapsulation material for energy storage devices disclosed herein is suitable for use as an encapsulation material for secondary batteries such as lithium-ion batteries, nickel-metal hydride batteries, and lead-acid batteries, as well as electrochemical capacitors such as electric double-layer capacitors. In particular, the encapsulation material for energy storage devices disclosed herein is suitable for use as an encapsulation material for all-solid-state batteries using solid electrolytes.

[0197] [Electronic Storage Device]

[0198] Figure 3 A perspective view illustrating one embodiment of an energy storage device made using the aforementioned encapsulation material. (See attached image.) Figure 3As shown, the energy storage device 50 is configured to include: a battery element (energy storage device body) 52, two metal terminals (current output terminals) 53 for outputting current from the battery element 52, and an encapsulation material 10 that encapsulates the battery element 52 in an airtight state. The encapsulation material 10 is the encapsulation material 10 described in this embodiment. In the encapsulation material 10, the substrate layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, for the encapsulation material 10, the battery element 52 is internally encapsulated by folding and heat-sealing one laminated film or by overlapping and heat-sealing two laminated films, so that the substrate layer 11 is the outer side of the energy storage device 50 and the sealant layer 16 is the inner side of the energy storage device 50. It should be noted that the encapsulation material 20 can also be used instead of the encapsulation material 10 in the energy storage device 50.

[0199] The battery element 52 is formed by sandwiching an electrolyte between the positive and negative electrodes. The metal terminal 53 is formed by a portion of the current collector extending outside the encapsulation material 10, and is made of metal foil such as copper foil or aluminum foil.

[0200] The energy storage device 50 of this embodiment can be an all-solid-state battery. In this case, a solid electrolyte such as a sulfide-based solid electrolyte can be used as the electrolyte for the battery element 52. The energy storage device 50 of this embodiment uses the encapsulation material 10 of this embodiment, thus ensuring excellent lamination strength even when used in high-temperature environments.

[0201] The Second Aspect

[0202] The encapsulation material for the energy storage device according to the second aspect of this disclosure will be described. Descriptions of commonalities with the encapsulation material for the energy storage device according to the first aspect are omitted. The manufacturing method and the energy storage device according to the second aspect are the same as those according to the first aspect, therefore descriptions are omitted.

[0203] Encapsulation materials for energy storage devices

[0204] The first adhesive layer 12a in the energy storage device packaging material of the second aspect is different from that in the energy storage device packaging material of the first aspect.

[0205] <First adhesive layer 12a>

[0206] The first adhesive layer 12a is a layer that bonds the substrate layer 11 and the barrier layer 13 together. In the encapsulation material 10 of this embodiment, the first adhesive layer 12a contains a urethane resin formed by at least one polyol selected from the group consisting of polyether polyol, polyester polyol, acrylic polyol and polycarbonate diol and a polyfunctional isocyanate compound, wherein the polyfunctional isocyanate compound is composed of at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing aromatic rings in their molecular structure.

[0207] Furthermore, when the substrate layer 11 is peeled off to expose the first adhesive layer 12a, and the attenuated total internal reflection of the exposed first adhesive layer 12a is measured by Fourier transform infrared spectroscopy from the outermost surface of the exposed first adhesive layer 12a, the baseline transmittance T0 at 2100 cm⁻¹... -1 Up to 2400cm -1 The minimum transmittance T1 detected within the range of 1670 cm⁻¹ -1 Up to 1700cm -1 The minimum transmittance T2 detected within the range satisfies the relationship 0.06≤(T0-T1) / (T0-T2)≤0.4.

[0208] In the IR spectrum obtained by attenuated total reflectance measurement using Fourier transform infrared spectroscopy, at 2100 cm⁻¹ -1 Up to 2400cm -1 The peak detected within the range is from the carbonyl group of the isocyanate group, at 1670 cm⁻¹. -1 Up to 1700cm -1 The peaks detected within the specified range are those originating from the carbonyl groups of the urethane bonds. When the ratio of isocyanate groups to urethane bonds satisfies 0.06 ≤ (T0-T1) / (T0-T2) ≤ 0.4, urea resin and biuret resin are formed by the reaction of unreacted isocyanate groups and a portion of the curing agent in the adhesive layer. Due to the active hydrogen groups present in the urea resin and biuret resin, the tensile strength and elongation at break of the adhesive layer are close to the values ​​of each layer (mainly the barrier layer and the substrate), resulting in improved moldability. Furthermore, when the molded article of this disclosure is exposed to a high-temperature environment (150°C), the reaction between the unreacted curing agents can be promoted. Due to the increase in urea resin and biuret resin, the Tg of the adhesive layer increases, thereby improving heat resistance.

[0209] Conversely, when (T0-T1) / (T0-T2) < 0.06, two modes exist: a mode where the main agent and curing agent react quantitatively under the condition of NCO / OH ≒ 1.0; or a mode where the curing agents react quantitatively with each other under the condition of NCO / OH > 1.0. In the former case, the Tg of the adhesive layer is significantly lower than the Tg at high temperature (150℃), thus coagulation failure occurs in the adhesive layer. In the latter case, during the aging stage, almost all the curing agents react, and compared with the adhesive layer satisfying 0.06 ≤ (T0-T1) / (T0-T2) ≤ 0.4, the brittleness increases, resulting in a significant decrease in formability.

[0210] Furthermore, when (T0-T1) / (T0-T2) > 0.4, it can be observed that there is an excess of unreacted curing agent in the adhesive layer. When this adhesive layer is exposed to a high-temperature environment, foaming may occur due to the reaction between the excess curing agents. Consequently, delamination occurs at high temperatures, thus reducing heat resistance.

[0211] The polyfunctional isocyanate compound used in the first adhesive layer 12a is the same as in the first aspect. In the first adhesive layer 12a, the ratio (NCO / OH) of the number of isocyanate groups in the polyfunctional isocyanate compound to the number of hydroxyl groups in the polyester polyol resin is the same as in the first aspect. The thickness of the first adhesive layer 12a is the same as in the first aspect. The mass per unit area of ​​the first adhesive layer 12a is the same as in the first aspect.

[0212] The Third Aspect

[0213] The encapsulation material and energy storage device according to the third aspect of this disclosure will be described. Descriptions of commonalities with the encapsulation material and energy storage device according to the first aspect are omitted. The manufacturing method of the energy storage device according to the third aspect is the same as that of the energy storage device according to the first aspect, therefore, descriptions are omitted.

[0214] Encapsulation materials for energy storage devices

[0215] The first adhesive layer 12a in the energy storage device packaging material of the third aspect is different from that in the energy storage device packaging material of the first aspect.

[0216] <First adhesive layer 12a>

[0217] The first adhesive layer 12a is a layer that bonds the substrate layer 11 and the barrier layer 13 together. In this disclosure, the first adhesive layer 12a needs to contain a polyurethane-based compound and a polyamide-imide resin. The adhesive layer containing the polyurethane-based compound has high toughness, and can obtain excellent deep-drawing formability and excellent lamination strength at room temperature. On the other hand, the polyamide-imide resin has excellent heat resistance. By mixing it with the above-mentioned polyurethane-based compound to form the adhesive layer, sufficient lamination strength between the substrate layer 11 and the barrier layer 13 and excellent deep-drawing formability of the encapsulation material 10 can be obtained at high temperature environments, such as above 170°C. Even in the encapsulation material 10 after deep drawing, the high lamination strength between the substrate layer 11 and the barrier layer 13 can be maintained at high temperature environments.

[0218] When the solid content of the above-mentioned polyamide-imide resin is set as A by mass% relative to the solid content of the polyurethane compound, it is preferable to satisfy 1.0 by mass% < A < 20.0 by mass%, and particularly preferable to satisfy 10.0 by mass% < A < 20.0 by mass%. In addition, the number average molecular weight Mn of the polyamide-imide resin is preferably 3000 < Mn < 36000.

[0219] Next, the polyurethane compound can be composed of the reaction product of at least one polyol resin and at least one polyfunctional isocyanate compound. The type of polyol resin can be arbitrary, but preferably at least one polyol resin selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate polyols. In this case, both the lamination strength between the substrate layer 11 and the barrier layer 13 at high temperatures and the moldability of the encapsulation material 10 are improved.

[0220] Furthermore, the type of the aforementioned polyfunctional isocyanate compound can be arbitrary, but it is preferable to use at least one isocyanate polymer selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing aromatic rings in their molecular structure. In this case, both lamination strength and moldability are improved.

[0221] As an alicyclic isocyanate polymer, for example, the isocyanurate form of isophorone diisocyanate (IPDI-isocyanurate) can be exemplified.

[0222] Furthermore, examples of isocyanate polymers containing an aromatic ring in their molecular structure include the adduct of toluene diisocyanate (TDI-adduct). Other examples include the adduct of diphenylmethane diisocyanate, biuret, and isocyanurate. Additionally, examples of isocyanate polymers containing an aromatic ring in their molecular structure include the adduct of phenylenediethylene diisocyanate, biuret, and isocyanurate.

[0223] It should be noted that a polyurethane-based compound is preferred, which is generated by reacting a polyester polyol as at least a portion of the polyol resin and an IPDI-isocyanurate as at least a portion of the polyfunctional isocyanate compound. In this way, the encapsulation material 10 having a first adhesive layer 12a comprising a polyurethane-based compound composed of the reaction product of the polyester polyol and the IPDI-isocyanurate exhibits particularly excellent lamination strength between the substrate layer 11 and the barrier layer 13 at high temperatures, as well as excellent moldability of the encapsulation material 10.

[0224] In a specific adhesive layer, the content of isocyanate groups from IPDI-isocyanurate in the polyfunctional isocyanate compound is the same as in aspect 1.

[0225] In a specific adhesive layer, the ratio (NCO / OH) of the amount of isocyanate contained in the aforementioned polyfunctional isocyanate compound to the amount of hydroxyl groups contained in the polyol resin is preferably 1.5 < NCO / OH < 40.0. When the amount of isocyanate contained in the curing agent (polyfunctional isocyanate compound) of the polyurethane compound is sufficiently greater than the amount of hydroxyl groups contained in the main agent (polyol resin) (NCO / OH >> 1.0), the heat resistance is improved. It should be noted that when the polyurethane compound is composed of the reaction product of polyester polyol and IPDI-isocyanurate, the optimal value of NCO / OH is 20.

[0226] [Electronic Storage Device]

[0227] Figure 3 A perspective view illustrating one embodiment of an energy storage device made using the aforementioned encapsulation material. (See attached image.) Figure 3As shown, the energy storage device 50 is configured to include: a battery element (energy storage device body) 52, two metal terminals (current output terminals) 53 for outputting current from the battery element 52 to the outside, and an encapsulation material 10 that encapsulates the battery element 52 in an airtight state. The encapsulation material 10 is the encapsulation material 10 described in this embodiment. In the encapsulation material 10, the substrate layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, for the encapsulation material 10, it is folded in such a way that the substrate layer 11 becomes the outer side of the energy storage device 50 and the sealant layer 16 becomes the inner side of the energy storage device 50, and then deep-drawn on one side, and then heat-fused to form a configuration in which the battery element 52 is internally housed and sealed. Alternatively, one of the two encapsulation materials 10 is deep-drawn, and then overlapped with the other encapsulation material 10 and heat-fused, thereby also forming an energy storage device 50 that internally houses and seals the battery element 52. It should be noted that in the energy storage device 50, the encapsulation material 20 can be used instead of the encapsulation material 10.

[0228] In the energy storage device involved in the third aspect, other aspects are the same as those involved in the energy storage device involved in the first aspect.

[0229] The Fourth Aspect

[0230] The fourth aspect of this disclosure relates to the encapsulation material for an energy storage device, a method for manufacturing the encapsulation material, and the energy storage device.

[0231] Encapsulation materials for energy storage devices

[0232] Figure 4 A cross-sectional view illustrating one embodiment of the encapsulation material for energy storage devices of this disclosure. (See diagram below.) Figure 4 As shown, the encapsulation material (encapsulation material for energy storage devices) 25 of this embodiment is a laminate, which comprises: a substrate layer 11, a first adhesive layer 12 disposed on one surface of the substrate layer 11, a barrier layer 13 disposed on the side of the first adhesive layer 12 opposite to the substrate layer 11 and having anti-corrosion treatment layers 14a and 14b on both sides, a second adhesive layer 17 disposed on the side of the barrier layer 13 opposite to the first adhesive layer 12, and a sealant layer 16 disposed on the side of the second adhesive layer 17 opposite to the barrier layer 13. Here, the anti-corrosion treatment layer 14a is disposed on the surface of the barrier layer 13 on the side of the first adhesive layer 12, and the anti-corrosion treatment layer 14b is disposed on the surface of the barrier layer 13 on the side of the second adhesive layer 17. In the encapsulation material 25, the substrate layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the encapsulation material 25 is used such that the substrate layer 11 faces the outside of the energy storage device and the sealant layer 16 faces the inside of the energy storage device. Hereinafter, each layer will be described.

[0233] <Substrate Layer 11>

[0234] The substrate layer 11 serves the following functions: imparting heat resistance during the sealing process in the manufacture of energy storage devices, and suppressing pinholes during molding and distribution. Particularly for encapsulation materials in large-scale energy storage devices, it can also impart scratch resistance, chemical resistance, and insulation.

[0235] The melting peak temperature of the substrate layer 11 is preferably higher than that of the sealant layer 16. By making the melting peak temperature of the substrate layer 11 higher than that of the sealant layer 16, appearance deterioration caused by melting of the substrate layer 11 (the outermost layer) during heat sealing can be suppressed. When the sealant layer 16 has a multilayer structure, the melting peak temperature of the sealant layer 16 refers to the melting peak temperature of the layer with the highest melting peak temperature. The melting peak temperature of the substrate layer 11 is preferably 290°C or higher, more preferably 290–350°C. Examples of resin films that can be used as the substrate layer 11 and have melting peak temperatures within the above range include: nylon films, PET films, polyamide films, polyphenylene sulfide (PPS) films, polyimide films, polyester films, etc. The melting peak temperature refers to the value obtained according to the method described in JIS K7121-1987.

[0236] As the substrate layer 11, a commercially available film can be used, or the substrate layer 11 can be formed by coating (coating and drying of the coating solution). It should be noted that the substrate layer 11 can be a single-layer structure or a multi-layer structure, and can be formed by coating a thermosetting resin. In addition, the substrate layer 11 can contain various additives such as flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.

[0237] The peak melting temperature T of the substrate layer 11 11 The peak melting temperature T of sealant layer 16 16 The difference (T) 11 -T 16 The temperature difference is preferably 20°C or higher. By maintaining this temperature difference at 20°C or higher, the degradation of the appearance of the encapsulation material 20 caused by heat sealing can be further and sufficiently suppressed. The thickness of the substrate layer 11 is preferably 5 to 50 μm, more preferably 12 to 30 μm.

[0238] <First adhesive layer 12 and second adhesive layer 17>

[0239] The first adhesive layer 12 and the second adhesive layer 17 will be described in detail below.

[0240] (First adhesive layer 12)

[0241] The first adhesive layer 12 is a layer that bonds the barrier layer 13, to which the anti-corrosion treatment layer 14a is provided, to the substrate layer 11. The first adhesive layer 12 has the adhesive force required to firmly bond the substrate layer 11 and the barrier layer 13 together, and also has a conformability that prevents the barrier layer 13 from breaking due to the substrate layer 11 during cold forming. It should be noted that the conformability is such that even if the part deforms due to expansion or contraction, the first adhesive layer 12 will not peel off but will remain on the part.

[0242] Examples of adhesive components forming the first adhesive layer 12 include urea-based compounds and urethane-based compounds. These compounds can be used alone or in combination of two or more. Urea-based compounds are obtained by reacting amine resins as the main agent with polyisocyanate compounds as the curing agent. Urethane-based compounds are obtained by reacting polyols as the main agent with polyisocyanate compounds as the curing agent.

[0243] Examples of amine resins include polyacrylamide.

[0244] Examples of polyols include polyester polyols, polyether polyols, and acrylic polyols.

[0245] Polyester polyols include, for example, polyester polyols obtained by reacting one or more dicarboxylic acids with a diol.

[0246] Examples of polyether polyols include substances manufactured by addition polymerization of ethylene oxide, propylene oxide, propylene glycol, glycerol, pentaerythritol, etc.

[0247] Examples of acrylic polyols include copolymers obtained by copolymerizing hydroxyl-containing acrylic monomers with (meth)acrylic acid. In this case, it is preferable to include structural units derived from (meth)acrylic acid as the main component. Examples of hydroxyl-containing acrylic monomers include 2-hydroxyethyl (meth)acrylic acid and 2-hydroxypropyl (meth)acrylic acid.

[0248] Polyisocyanate compounds contain multiple isocyanate groups and function to crosslink the aforementioned amine resins or polyols. Polyisocyanate compounds can be used alone or in combination of two or more. Examples of polyisocyanate compounds include, for example, aliphatic polyisocyanate compounds, alicyclic polyisocyanate compounds, and aromatic polyisocyanate compounds.

[0249] Examples of aliphatic polyisocyanate compounds include hexamethylene diisocyanate (HDI) and phenylenediamine diisocyanate (XDI). Examples of alicyclic polyisocyanate compounds include isophorone diisocyanate (IPDI). Examples of aromatic polyisocyanate compounds include toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI). Polyisocyanate compounds can be polymers (e.g., trimers) of these compounds; specifically, adducts, biuret forms, isocyanurates, etc., can be used.

[0250] To improve the pot life of polyisocyanate compounds, it is preferable that their isocyanate groups are bonded to a capping agent. Examples of capping agents include methyl ethyl ketone oxime (MEKO). The temperature at which the capping agent detaches from the isocyanate groups of the polyisocyanate compound can be 50°C or higher, and for further improving the pot life, 60°C or higher is preferred. The temperature at which the capping agent detaches from the isocyanate groups of the polyisocyanate compound can be 140°C or lower, and for improving the molding and curl resistance of the encapsulation material, 120°C or lower is preferred.

[0251] To lower the dissociation temperature of the capping agent, a catalyst that reduces the dissociation temperature can be used. Examples of such catalysts include tertiary amines such as triethylenediamine and N-methylmorpholine, and organometallic acid salts such as dibutyltin dilaurate.

[0252] In urea compounds, the molar ratio of the isocyanate group of the polyisocyanate compound to the amino group of the amine resin is preferably 1 to 10, more preferably 2 to 5. In urethane compounds, the molar ratio of the isocyanate group of the polyisocyanate compound to the hydroxyl group of the polyol is preferably 1 to 50, more preferably 10 to 30.

[0253] The first adhesive layer 12 preferably contains a hydrogen sulfide adsorbent, thereby suppressing corrosion of the barrier layer 13 caused by hydrogen sulfide present on the exterior of the encapsulation material. Examples of such hydrogen sulfide adsorbents include zinc oxide and potassium permanganate. When the first adhesive layer 12 contains a hydrogen sulfide adsorbent, its content is preferably 1 to 50% by mass relative to the total amount of the first adhesive layer 12, in order to suppress corrosion of the barrier layer 13 caused by hydrogen sulfide present on the exterior of the encapsulation material.

[0254] From the viewpoint of obtaining the desired adhesive strength, conformability, and processability, the thickness of the first adhesive layer 12 is preferably 1 to 10 μm, more preferably 2 to 6 μm.

[0255] The first adhesive layer 12 can be obtained, for example, by coating a composition containing the above-mentioned adhesive components and a curing agent. Known methods can be used for coating, such as direct gravure printing, reverse gravure printing (direct, kiss-type), and micro-gravure printing.

[0256] When the first adhesive layer 12 contains a urea compound, the proportion of the amine resin in the composition containing the amine resin and the polyisocyanate compound is preferably 1 to 10 by mass relative to the total amount of the amine resin and the polyisocyanate compound.

[0257] When the first adhesive layer 12 contains a carbamate compound, the proportion of polyol in the composition containing polyol and polyisocyanate compound is preferably 50 to 80 by mass relative to the total amount of polyol and polyisocyanate compound.

[0258] (Second adhesive layer 17)

[0259] The second adhesive layer 17 is a layer that bonds the barrier layer 13, which has an anti-corrosion treatment layer 14b, to the sealant layer 16.

[0260] As adhesive components forming the second adhesive layer 17, the same adhesive components listed in the first adhesive layer 12 can be used, for example.

[0261] The second adhesive layer 17 preferably contains a hydrogen sulfide adsorbent, thereby suppressing corrosion of the barrier layer 13 caused by hydrogen sulfide generated from the battery contents inside the encapsulation material. Such a hydrogen sulfide adsorbent can be the same as that listed in the first adhesive layer 12. Furthermore, its content is preferably 0.1 to 50% by mass relative to the total amount of the second adhesive layer 17.

[0262] The second adhesive layer 17 can be obtained by the same method as the first adhesive layer 12. When the second adhesive layer 17 contains a urea compound, the proportion of the amine resin in the composition containing the amine resin and the polyisocyanate compound can be the same as in the first adhesive layer 12. When the second adhesive layer 17 contains a urethane compound, the proportion of the polyol in the composition containing the polyol and the polyisocyanate compound can be the same as in the first adhesive layer 12.

[0263] The thickness of the second adhesive layer 17 is preferably 1 to 5 μm. Since the thickness of the second adhesive layer 17 is 1 μm or more, it is easy to obtain sufficient adhesive strength between the barrier layer 13 and the sealant layer 16; since it is 5 μm or less, cracking of the second adhesive layer 17 can be suppressed.

[0264] At least one of the first adhesive layer 12 and the second adhesive layer 17 contains a urea compound as a reaction product of an amine resin and a polyisocyanate compound, and in the layers containing the urea compound in the first adhesive layer 12 and the second adhesive layer 17, when 1680-1720 cm -1 The infrared absorption spectrum peak intensity was set to A1, and the range of 1590–1640 cm⁻¹ was... -1 When the infrared absorption spectrum peak intensity is set to B1, X1, defined by the following formula (1-A), is 10–99, preferably 20–80.

[0265] X1={B1 / (A1+B1)}×100…(1-A)

[0266] The first adhesive layer 12 and the second adhesive layer 17 contain urea compounds in the 1680-1720 cm layer. -1 The infrared absorption spectrum peak intensity and 1590–1640 cm⁻¹ -1 The intensity of the infrared absorption spectrum peak can be determined by FT-IR (ATR method (total reflectance absorption infrared spectroscopy)).

[0267] The first adhesive layer 12 and the second adhesive layer 17 may both contain urea compounds, or only the first adhesive layer 12 may contain a urea compound, or only the second adhesive layer 17 may contain a urea compound. The resulting encapsulation material exhibits excellent heat resistance, easily mitigates the rigidity of the first adhesive layer, and has excellent deep-drawing properties. Therefore, it is preferable that the first adhesive layer 12 does not contain a urea compound, while only the second adhesive layer 17 contains a urea compound. When the first adhesive layer 12 contains a urea compound, the urea groups of the urea compound exert cohesive force, making it difficult for hydrogen sulfide present on the exterior of the encapsulation material to penetrate the first adhesive layer 12, thereby inhibiting corrosion of the barrier layer 13 caused by hydrogen sulfide. When the second adhesive layer 17 contains a urea compound, the urea groups of the urea compound exert cohesive force, making it difficult for hydrogen sulfide generated from the battery contents inside the encapsulation material to pass through the second adhesive layer 17, thus inhibiting the corrosion of the barrier layer 13 caused by hydrogen sulfide. Therefore, the second adhesive layer 17 preferably contains a urea compound.

[0268] <Barrier Layer 13>

[0269] The barrier layer 13 has water vapor barrier properties that prevent moisture from entering the interior of the energy storage device. Furthermore, the barrier layer 13 has ductility suitable for deep drawing. Various metal foils such as aluminum, stainless steel, and copper, or metal vapor-deposited films, inorganic oxide vapor-deposited films, carbon-containing inorganic oxide vapor-deposited films, and films containing these vapor-deposited films can be used as the barrier layer 13. For example, aluminum vapor-deposited films and inorganic oxide vapor-deposited films can be used. These can be used individually or in combination of two or more. From the perspectives of mass (specific gravity), moisture resistance, processability, and cost, metal foil is preferred as the barrier layer 13, and aluminum foil is more preferred.

[0270] From the perspective of imparting the desired ductility during molding, annealed soft aluminum foil is particularly preferred as the aluminum foil. However, to further impart resistance to pinholes and ductility during molding, iron-containing aluminum foil is more preferred. The iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass, in 100% by mass aluminum foil (e.g., aluminum foil made of JIS standard 8021 or 8079 materials). By making the iron content 0.1% by mass or more, a packaging material 25 with superior resistance to pinholes and ductility can be obtained. By making the iron content 9.0% by mass or less, a packaging material 25 with superior flexibility can be obtained.

[0271] To obtain the desired electrolyte resistance, it is preferable to degrease the metal foil used in the barrier layer 13. Furthermore, to simplify the manufacturing process, it is preferable to use a metal foil whose surface is not etched. Specifically, for the metal foil used in the barrier layer 13, degreased aluminum foil is preferred in terms of imparting electrolyte resistance. When degreasing the aluminum foil, it can be performed on only one side or on both sides. For example, wet degreasing or dry degreasing can be used, but from the viewpoint of simplifying the manufacturing process, dry degreasing is preferred.

[0272] As an example of the aforementioned dry degreasing treatment, the following method can be used: during the annealing process of the metal foil, degreasing is performed by extending the treatment time. Even when degreasing is performed simultaneously with the annealing process to soften the metal foil, sufficient electrolyte resistance can be obtained.

[0273] Furthermore, as the aforementioned dry degreasing process, treatments other than the annealing process described above, such as flame treatment and corona treatment, can be used. Additionally, as the aforementioned dry degreasing process, for example, a degreasing process that uses active oxygen generated when ultraviolet light of a specific wavelength is irradiated onto the metal foil to oxidize, decompose, and remove contaminants can be used.

[0274] As for the aforementioned wet degreasing treatment, acid degreasing, alkaline degreasing, or similar treatments can be used. For the acid degreasing treatment, inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid can be used. These acids can be used alone or in combination of two or more. Furthermore, for the alkaline degreasing treatment, sodium hydroxide, which has a high etching effect, can be used. Alkaline degreasing can also be performed using a mixture of a weakly alkaline material and a surfactant. The wet degreasing treatment described above can be performed, for example, by immersion or spraying.

[0275] From the perspectives of barrier properties, pinhole resistance, and processability, the thickness of the barrier layer 13 is preferably 9–200 μm, more preferably 15–150 μm, and even more preferably 15–100 μm. Since the thickness of the barrier layer 13 is 9 μm or more, it is difficult to break even when stress is applied during molding. Since the thickness of the barrier layer 13 is 200 μm or less, the increase in the mass of the encapsulation material can be reduced, thereby suppressing the decrease in the weight energy density of the energy storage device.

[0276] <Anti-corrosion treatment layers 14a, 14b>

[0277] The anti-corrosion treatment layers 14a and 14b are layers disposed on the surface of the metal thin layer constituting the barrier layer 13 to prevent corrosion. Furthermore, the anti-corrosion treatment layer 14a enhances the adhesion between the barrier layer 13 and the first adhesive layer 12. Furthermore, the anti-corrosion treatment layer 14b enhances the adhesion between the barrier layer 13 and the second adhesive layer 17. The anti-corrosion treatment layers 14a and 14b may be layers of the same or different compositions. In this embodiment, anti-corrosion treatment layers are disposed between the barrier layer 13 and the first adhesive layer 12, and between the barrier layer 13 and the second adhesive layer 17; however, it is also possible to dispose of the anti-corrosion treatment layers only between the barrier layer 13 and the second adhesive layer 17.

[0278] The anti-corrosion treatment layers 14a and 14b can be formed, for example, by degreasing, hydrothermal modification, anodizing, chemical conversion, coating with an anti-corrosion agent, or a combination of these treatments on the base material layer serving as the anti-corrosion treatment layers 14a and 14b.

[0279] Among the above-mentioned treatments, degreasing, hydrothermal modification, and anodizing, especially hydrothermal modification and anodizing, involve dissolving the surface of the metal foil (aluminum foil) using a treatment agent to form a metal compound (aluminum compound (boehmite, aluminate)) with excellent corrosion resistance. Therefore, in order to obtain a structure that forms a continuous structure from the barrier layer 13 to the anti-corrosion treatment layers 14a and 14b, such treatments are sometimes included in the definition of chemical conversion treatment.

[0280] As a degreasing treatment, acid degreasing and alkali degreasing can be cited. For acid degreasing, methods such as using inorganic acids like sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid alone, or a mixture thereof, can be cited. Furthermore, as an acid degreasing agent, by dissolving a fluorine-containing compound such as sodium difluoride in the aforementioned inorganic acid, not only can the degreasing effect of the barrier layer 13 be obtained, but a passive metal fluoride can also be formed, thus being effective in terms of resistance to hydrofluoric acid. For alkali degreasing, methods using sodium hydroxide, etc., can be cited.

[0281] As a hydrothermal modification treatment, boehmite treatment, obtained by impregnating the barrier layer 13 in boiling water with added triethanolamine, can be used, for example. As an anodizing treatment, aluminate treatment can be used, for example. Furthermore, as a chemical conversion treatment, chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or a combination of two or more of these can be used. These hydrothermal modification treatments, anodizing treatments, and chemical conversion treatments are preferably preceded by the aforementioned degreasing treatment.

[0282] It should be noted that the aforementioned chemical conversion treatment is not limited to wet methods; for example, methods using these treatments can be employed such as mixing the treatment agents with resin components and then coating them. Furthermore, from the viewpoint of maximizing the effectiveness and treating wastewater, coating-type chromate treatment is preferred as the aforementioned anti-corrosion treatment.

[0283] As a coating agent used in coating-type anti-corrosion treatment, examples include coating agents containing at least one selected from the group consisting of rare earth element oxide sols, anionic polymers, and cationic polymers. Methods using coating agents containing rare earth element oxide sols are particularly preferred.

[0284] The preferred mass per unit area of ​​the anti-corrosion treatment layers 14a and 14b is 0.005–0.200 g / m². 2 Within the range, more preferably within 0.010 to 0.100 g / m 2 Within the range. If it is 0.005g / m 2The above methods easily impart anti-corrosion properties to the barrier layer 13. Furthermore, even if the mass per unit area exceeds 0.200 g / m²... 2 The corrosion resistance has reached saturation, so better results cannot be expected. It should be noted that the above description lists the mass per unit area, but if the specific gravity is known, it can be converted into thickness.

[0285] From the perspective of corrosion protection and function as an anchoring layer, the thickness of the corrosion protection layers 14a and 14b is preferably 10 nm to 5 μm, and more preferably 20 to 500 nm.

[0286] <Sealant Layer 16>

[0287] The sealant layer 16 is a layer that imparts heat-sealing properties to the encapsulation material 25. It is a layer that is placed on the inside and heat-sealed (heat-fused) during the assembly of the energy storage device.

[0288] As the sealant layer 16, for example, a film made of acrylic resin, polyolefin resin or polyester resin can be cited. Since the sealant layer 16 has a high melting point, the heat resistance of the resulting encapsulation material is further improved. Therefore, a film made of polyolefin resin or polyester resin is preferred, and a film made of polyester resin is more preferred.

[0289] Examples of acrylic resins include polymethyl methacrylate (PMMA). These acrylic resins can be used alone or in combination of two or more.

[0290] Examples of polyolefin resins include low-density, medium-density, and high-density polyethylene, ethylene-α-olefin copolymers, polypropylene, and propylene-α-olefin copolymers. Polyolefin resins used as copolymers can be either block copolymers or random copolymers.

[0291] Examples of polyester resins include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). These polyester resins can be used alone or in combination of two or more.

[0292] The sealant layer 16 can be a single-layer film or a multi-layer film, depending on the required function. When the sealant layer 16 is composed of multiple layers, the layers can be stacked together by co-extrusion or by dry lamination.

[0293] The sealant layer 16 may contain various additives such as flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, and tackifiers.

[0294] The thickness of the sealant layer 16 is preferably 10 to 100 μm, more preferably 20 to 60 μm. Since the thickness of the sealant layer 16 is 10 μm or more, sufficient heat-sealing strength can be obtained; since it is 100 μm or less, the amount of water vapor that can be immersed from the end of the encapsulation material can be reduced.

[0295] From the perspective of improving heat resistance, the melting peak temperature of the sealant layer 16 is preferably 200-280℃.

[0296] [Manufacturing methods for encapsulation materials]

[0297] Next, the manufacturing method of the encapsulation material 25 will be described. It should be noted that the manufacturing method of the encapsulation material 25 is not limited to the following method.

[0298] As a method for manufacturing the encapsulation material 25, for example, a method that sequentially performs the following steps S11 to S13 can be listed.

[0299] Process S11: The process of forming an anti-corrosion treatment layer 14a on one surface of the barrier layer 13 and forming an anti-corrosion treatment layer 14b on the other surface of the barrier layer 13.

[0300] Process S12: A process of bonding the surface of the anti-corrosion treatment layer 14a opposite to the barrier layer 13 to the substrate layer 11 via the first adhesive layer 12.

[0301] Step S13: A step of forming a sealant layer 16 on the surface of the anti-corrosion treatment layer 14b opposite to the barrier layer 13 via the second adhesive layer 17.

[0302] <Process S11>

[0303] In step S11, an anti-corrosion treatment layer 14a is formed on one surface of the barrier layer 13, and an anti-corrosion treatment layer 14b is formed on the other surface of the barrier layer 13. The anti-corrosion treatment layers 14a and 14b can be formed separately or simultaneously. Specifically, for example, anti-corrosion treatment layers 14a and 14b can be formed simultaneously by coating both surfaces of the barrier layer 13 with an anti-corrosion treatment agent (the base material of the anti-corrosion treatment layer), followed by sequential drying, curing, and firing. Alternatively, an anti-corrosion treatment agent can be coated on one surface of the barrier layer 13, followed by sequential drying, curing, and firing to form anti-corrosion treatment layer 14a, and then anti-corrosion treatment layer 14b can be formed similarly on the other surface of the barrier layer 13. There are no particular restrictions on the formation order of the anti-corrosion treatment layers 14a and 14b. Furthermore, regarding the anti-corrosion treatment agent, anti-corrosion treatment layers 14a and 14b can use different substances or the same substance. There are no particular limitations on the application method of the anti-corrosion agent. For example, the following methods can be used: gravure coating, gravure reverse coating, roller coating, reverse roller coating, mold coating, bar coating, kiss coating, comma coating, small-diameter gravure coating, etc.

[0304] <Process S12>

[0305] In step S12, the surface of the anti-corrosion treatment layer 14a opposite to the barrier layer 13 is bonded to the substrate layer 11 using an adhesive that forms the first adhesive layer 12 and by methods such as dry lamination. In step S12, a heat treatment can be performed to improve the adhesion of the first adhesive layer 12. From the perspective of excellent moldability and curl resistance of the encapsulation material, the heat treatment temperature is preferably below 140°C; from the perspective of improving the pot life of the end-capping agent, the heat treatment temperature is preferably above 60°C.

[0306] <Process S13>

[0307] After step S12, using the adhesive that forms the second adhesive layer 17, and employing methods such as dry lamination, the surface of the anti-corrosion treatment layer 14b, which consists of a substrate layer 11, a first adhesive layer 12, an anti-corrosion treatment layer 14a, a barrier layer 13, and an anti-corrosion treatment layer 14b stacked sequentially, opposite to the barrier layer 13, is bonded to the sealant layer 16. In step S13, a heat treatment can be performed to improve the adhesion of the second adhesive layer 17. From the perspective of excellent moldability and curl resistance of the encapsulation material, the heat treatment temperature is preferably 140°C or lower, more preferably 120°C or lower; from the perspective of improving the pot life of the sealing agent, the heat treatment temperature is preferably 60°C or higher.

[0308] According to the processes S11 to S13 described above, the encapsulation material 25 can be obtained. It should be noted that the process sequence of manufacturing the encapsulation material 25 is not limited to performing processes S11 to S13 sequentially. The order of the processes can be appropriately changed; for example, process S12 can be performed first, followed by process S11.

[0309] [Electronic Storage Devices]

[0310] Next, an energy storage device having an encapsulation material 25 as a container will be described. The energy storage device includes: a battery element 1 containing electrodes, leads 2 extending from the electrodes, and a container housing the battery element 1. The container is formed from the encapsulation material 25 of the energy storage device, with a sealant layer 16 as the inner side. The container can be obtained by overlapping two encapsulation materials with the sealant layer 16 facing each other and heat-sealing the periphery of the overlapped encapsulation material 25. Alternatively, it can be obtained by folding one encapsulation material in half and overlapping it, and similarly heat-sealing the periphery of the encapsulation material 25. The leads 2 are held and sealed by the encapsulation material 25, which forms the container with the sealant layer 16 as the inner side. The leads 2 can be held by the encapsulation material 25 via a tab sealant.

[0311] The encapsulation material of this embodiment can be used in various energy storage devices. Examples of such energy storage devices include secondary batteries such as lithium-ion batteries, nickel-metal hydride batteries, lead-acid batteries, and all-solid-state batteries, as well as electrochemical capacitors such as electric double-layer capacitors. The encapsulation material 25 of this embodiment maintains excellent heat-sealing properties even when used in high-temperature environments after heat sealing, and is therefore suitable for all-solid-state batteries that are expected to be used in such environments.

[0312] [Manufacturing Method for Energy Storage Devices]

[0313] Next, the method for manufacturing an energy storage device using the aforementioned encapsulation material 25 will be described. It should be noted that, here, the example of manufacturing a secondary battery 40 using embossed encapsulation material 30 will be used. Figure 5 A diagram illustrating the embossed encapsulation material 30 described above. Figure 6 (a) to (d) are perspective views of the manufacturing process of a single-sided molded battery using encapsulation material 25. The secondary battery 40 can be a double-sided molded battery manufactured as follows: two sheets of encapsulation material, such as embossed encapsulation material 30, are prepared and glued together while being aligned and adjusted.

[0314] The secondary battery 40, which is a single-sided molded battery, can be manufactured, for example, through the following processes S21 to S26.

[0315] Step S21: The process of preparing the encapsulation material 25, the battery element 1 containing the electrodes, and the lead wires 2 extending from the electrodes.

[0316] Step S22: A process in which a recess 32 for arranging the battery element 1 is formed on one side of the encapsulation material 25 to obtain the embossed encapsulation material 30 (see reference). Figure 6 (a) and Figure 6 (b)).

[0317] Step S23: A process in which the battery element 1 is placed in the molding area (recess 32) of the embossed encapsulation material 30, the embossed encapsulation material 30 is folded back and overlapped with the cover 34 covering the recess 32, and one side of the embossed encapsulation material 30 is heat-sealed by clamping the lead 2 extending from the battery element 1 (see reference). Figure 6 (b) and Figure 6 (c)).

[0318] Step S24: Leave one side except for the side holding lead 2, heat seal the other sides, then inject electrolyte from the left side and heat seal the left side under vacuum (refer to the step S24). Figure 6 (c)).

[0319] Process S25: A process of charging and discharging under predetermined conditions such as current, voltage, and ambient temperature to cause a chemical change (chemical conversion).

[0320] Step S26: The process of cutting the end of the heat-sealed edge (excluding the edge holding the lead wire 2) and bending it towards the forming processing area (recess 32) (see reference). Figure 6 (d)).

[0321] <Process S21>

[0322] In step S21, encapsulation material 25, battery element 1 including electrodes, and leads 2 extending from the electrodes are prepared. Encapsulation material 25 is prepared based on the above embodiment. There are no particular limitations on the battery element 1 and leads 2, and known battery element 1 and leads 2 can be used.

[0323] <Process S22>

[0324] In step S22, a recess 32 for arranging the battery element 1 is formed on the sealant layer 16 side of the encapsulation material 25. The planar shape of the recess 32 can be a shape consistent with the shape of the battery element 1, for example, a rectangle in a plan view. The recess 32 is formed, for example, by pressing a pressing member with a rectangular pressure surface relative to a portion of the encapsulation material 25 in its thickness direction. Furthermore, the pressing position, i.e., the recess 32 is formed at one end of the encapsulation material 25 further away from the center of the rectangular encapsulation material 25 in the longitudinal direction. Thus, the other end side, where the recess 32 is not formed after molding, can be folded back to serve as a cover (cover portion 34).

[0325] More specifically, a method for forming the recess 32 can be described using a molding process (deep drawing). As a molding method, the following method can be used: a female mold and a male mold are configured with a gap having a thickness greater than that of the encapsulation material 25, and the male mold and the encapsulation material 25 are pressed together into the female mold. By adjusting the amount of pressing in the male mold, the depth (deep drawing amount) of the recess 32 can be adjusted to a desired amount. By forming the recess 32 in the encapsulation material 25, an embossed encapsulation material 30 can be obtained. This embossed encapsulation material 30, for example, has the following characteristics: Figure 2 The shape shown. Here, Figure 5 (a) is a perspective view of the embossed encapsulation material 30. Figure 5 (b) along Figure 5 (a) shows a longitudinal section of the bb line of the embossed encapsulation material 30.

[0326] <Process S23>

[0327] In step S23, a battery element 1, consisting of a positive electrode, a separator, and a negative electrode, is disposed within the molding processing area (recess 32) of the embossed encapsulation material 30. Furthermore, leads 2 extending from the battery element 1 and respectively bonded to the positive and negative electrodes are pulled outward from the molding processing area (recess 32). Then, the embossed encapsulation material 30 is folded back approximately at its center in the longitudinal direction, overlapping the sealant layers 16 so that they are inside each other, and one side holding the leads 2 of the embossed encapsulation material 30 is heat-sealed. The heat sealing is controlled by three conditions: temperature, pressure, and time, and is appropriately set. The heat sealing temperature is preferably above the melting temperature of the sealant layer 16, specifically above 180°C.

[0328] After heat sealing, a further curing process is performed on the entire sealant layer 16 by heating. This promotes crystallization outside the heat-sealed area, thereby ensuring the overall heat resistance of the encapsulation material 25. The curing process can be carried out at 80–150°C.

[0329] It should be noted that the thickness of the sealant layer 16 before heat sealing is preferably 40% to 80% less than the thickness of the lead 2. Since the thickness of the sealant layer 16 is above the lower limit mentioned above, the resin constituting the sealant layer 16 tends to fully fill the end of the lead 2; since it is below the upper limit mentioned above, the thickness of the end of the encapsulation material 25 of the secondary battery 40 can be appropriately suppressed, thereby reducing the amount of moisture that seeps in from the end of the encapsulation material 25.

[0330] <Process S24>

[0331] In step S24, one side other than the side holding lead 2 is left unsealed, and the other sides are heat-sealed. Then, electrolyte is injected through the unsealed side, and the unsealed side is heat-sealed under vacuum. The heat-sealing conditions are the same as in step S23.

[0332] <Process S25>

[0333] In step S25, the secondary battery 40 obtained up to step S23 is charged and discharged to induce a chemical change (chemical conversion: 3 days at 40°C). Then, to remove the gas produced by the chemical conversion and replenish the electrolyte, the secondary battery 40 is reopened and finally sealed. It should be noted that step S25 can be omitted.

[0334] <Process S26>

[0335] The ends of the heat-sealed edges, except for the edge holding the lead 2, are cut off to remove the sealant layer 16 protruding from the ends. Then, the secondary battery 40 is obtained by folding the heat-sealed portion back toward the molding processing area 32 to form a folded portion 42.

[0336] The preferred embodiments of the encapsulation material for energy storage devices of the present invention have been described in detail above. However, the present invention is not limited to this embodiment, but various modifications and alterations can be made within the scope of the spirit of the present invention as set forth in the claims.

[0337] The Fifth Aspect

[0338] The fifth aspect of this disclosure describes the encapsulation material for the energy storage device, the method for manufacturing the encapsulation material, and the energy storage device. Descriptions of commonalities with the encapsulation material, energy storage device, and method for manufacturing the energy storage device described in the fourth aspect are omitted. The method for manufacturing the energy storage device described in the fifth aspect is the same as the method for manufacturing the energy storage device described in the fourth aspect; therefore, descriptions of this method are omitted.

[0339] Encapsulation materials for energy storage devices

[0340] The difference between the energy storage device packaging material according to the fifth aspect and the energy storage device packaging material according to the fourth aspect is that, in the energy storage device packaging material according to the fourth aspect, a barrier layer 13 is provided on the side of the first adhesive layer 12 opposite to the substrate layer 11, while in the energy storage device packaging material according to the fifth aspect, a metal foil layer is provided as the barrier layer 13. Furthermore, the first adhesive layer 12 is different in the energy storage device packaging material according to the fifth aspect and the energy storage device packaging material according to the fourth aspect.

[0341] (First adhesive layer 12)

[0342] The first adhesive layer 12 is a layer that bonds the metal foil layer, to which the anti-corrosion treatment layer 14a is provided, to the substrate layer 11. The first adhesive layer 12 has the adhesive force required to firmly bond the substrate layer 11 to the metal foil layer, and also has a tendency to resist breakage of the metal foil layer due to the substrate layer 11 during cold forming. It should be noted that this tendency is such that even if the part deforms due to expansion or contraction, the first adhesive layer 12 will not peel off but will remain on the part.

[0343] Examples of adhesive components forming the first adhesive layer 12 include urethane compounds and polyolefin resins. One or more adhesive components may be used alone or in combination. Urethane compounds can be obtained by reacting a polyol resin as the main agent with a polyisocyanate compound as the curing agent.

[0344] Examples of polyol-based resins include polyester polyol resins, polyether polyol resins, and acrylic polyol resins. Polyester polyol resins are preferred for improving the adhesion between the adhesive layer, sealant layer, and metal foil layer, and for resulting in better deep-drawing properties of the encapsulation material.

[0345] Examples of polyester polyol-based resins include resins obtained by reacting one or more dicarboxylic acids with a diol.

[0346] Examples of polyether polyol resins include those manufactured by addition polymerization of ethylene oxide, propylene oxide, propylene glycol, glycerol, pentaerythritol, etc.

[0347] Examples of acrylic polyol resins include copolymers obtained by copolymerizing hydroxyl-containing acrylic monomers with (meth)acrylic acid. In this case, structural units derived from (meth)acrylic acid are preferred as the main component. Examples of hydroxyl-containing acrylic monomers include 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.

[0348] Examples of polyolefin resins include: low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-α-olefin copolymer, homopolymer polypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0349] Polyolefin resins can be used that incorporate acidic groups to improve the adhesion between the substrate layer 11 and the metal foil layer. Examples of incorporated acidic groups include carboxyl groups and sulfonic acid groups, with carboxyl groups being particularly preferred.

[0350] As an acid-modified polyolefin resin obtained by introducing carboxyl groups into a polyolefin resin, examples include: acid-modified polyolefin resin obtained by grafting an unsaturated carboxylic acid or its anhydride, or an ester of an unsaturated carboxylic acid or its anhydride, onto a polyolefin resin in the presence of a free radical initiator.

[0351] Examples of unsaturated carboxylic acids include: acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclic [2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0352] Examples of acid anhydrides that are unsaturated carboxylic acids include: maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclic [2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.

[0353] Examples of esters of unsaturated carboxylic acids or their anhydrides include: methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconic acid, diethyl citrate, dimethyl tetrahydrophthalic anhydride, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.

[0354] The proportion of grafted compounds in acid-modified polyolefin resin is preferably 0.2 to 100 parts by weight relative to 100 parts by weight of polyolefin resin.

[0355] The polyisocyanate compound contains multiple isocyanate groups and functions to crosslink the aforementioned polyol-based resin. One or more polyisocyanate compounds can be used alone. Examples of polyisocyanate compounds include aliphatic, alicyclic, and aromatic polyisocyanate compounds; aromatic polyisocyanate compounds are preferred for improving the heat resistance of the resulting encapsulation material.

[0356] Examples of aliphatic polyisocyanate compounds include hexamethylene diisocyanate (HDI) and xylene diisocyanate (XDI). Examples of alicyclic polyisocyanate compounds include isophorone diisocyanate (IPDI). Examples of aromatic polyisocyanate compounds include toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI). Polyisocyanate compounds can be polymers (e.g., trimers) of these compounds; specifically, adducts, biuret compounds, and isocyanurate compounds can be used. From the perspective of improving the interfacial adhesion between the adhesive layer and the bonded object and improving the heat resistance of the resulting encapsulation material, adducts are preferred polyisocyanate compounds.

[0357] In urethane compounds, the molar ratio of the isocyanate group to the hydroxyl group of the polyisocyanate compound is preferably 1 to 50, more preferably 10 to 30.

[0358] When a polyol-based resin, acting as the main agent, reacts with a polyisocyanate compound, acting as a curing agent, a catalyst can be used to control the reaction. The polyisocyanate compound undergoes hydrolysis by reacting with moisture contained in the composition containing the main agent and curing agent, or in the atmosphere, to generate an amine compound. This amine compound further reacts with the polyisocyanate compound, potentially leading to self-condensation. However, by using a catalyst, these side reactions can be suppressed. As a result, the abundance ratio of urethane groups in the urethane-based compound in the first adhesive layer can be increased. Examples of such catalysts include organotin compounds such as dibutyltin and dioctyltin compounds, organotitanium compounds, and organozirconium compounds.

[0359] The first adhesive layer 12 preferably contains a hydrogen sulfide adsorbent, thereby suppressing corrosion of the metal foil layer caused by hydrogen sulfide present on the exterior of the encapsulation material. Examples of such hydrogen sulfide adsorbents include zinc oxide and potassium permanganate. Since the first adhesive layer 12 contains a hydrogen sulfide adsorbent, corrosion of the metal foil layer caused by hydrogen sulfide present on the exterior of the encapsulation material can be suppressed; therefore, its content is preferably 1 to 50% by mass relative to the total amount of the first adhesive layer 12.

[0360] From the viewpoint of obtaining the desired adhesive strength, conformability, and processability, the thickness of the first adhesive layer 12 is preferably 1 to 10 μm, more preferably 2 to 6 μm.

[0361] The first adhesive layer 12 can be obtained, for example, by coating a composition containing the aforementioned adhesive components and a curing agent. The coating method can be any known method, such as direct gravure printing, reverse gravure printing (direct, kiss-type), and micro-gravure printing.

[0362] When the first adhesive layer 12 contains a urethane compound, the proportion of the polyol resin in the composition containing the polyol resin and the polyisocyanate compound is preferably 50 to 90 by mass relative to the total amount of the polyol resin and the polyisocyanate compound.

[0363] When the first adhesive layer 12 contains a urethane compound and a catalyst is used when the polyol resin reacts with the polyisocyanate compound, the proportion of the catalyst in the composition containing the polyol resin, the polyisocyanate compound, and the catalyst is preferably 0.1 to 20% by mass relative to the total amount of the polyisocyanate compound.

[0364] When the first adhesive layer 12 contains an epoxy resin, the proportion of the polymer having two or more epoxy groups in the composition comprising a polymer having two or more epoxy groups in its molecule and a compound having a functional group that reacts with the epoxy groups is preferably 30 to 60 by mass relative to the total amount of these compounds.

[0365] <Metal Foil Layer>

[0366] Various metal foils, such as aluminum and stainless steel, can be used as the metal foil layer. However, considering factors such as moisture resistance, processability (e.g., ductility), and cost, aluminum foil is the preferred choice. While conventional soft aluminum foil can be used, iron-containing aluminum foil is preferred due to its superior resistance to pinholes and excellent ductility during forming.

[0367] In the iron-containing aluminum foil (100% by mass), the iron content is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass (e.g., aluminum foil made of JIS standard 8021 or 8079 materials). By making the iron content 0.1% by mass or more, a packaging material 25 with better pinhole resistance and ductility can be obtained. By making the iron content 9.0% by mass or less, a packaging material 25 with better flexibility can be obtained.

[0368] Furthermore, from the perspective of imparting the desired ductility during molding, soft aluminum foil that has undergone annealing is even more preferred as an aluminum foil.

[0369] To obtain the desired electrolyte resistance, it is preferable, for example, to degrease the metal foil used in the metal foil layer. Furthermore, to simplify the manufacturing process, it is preferable to use a metal foil whose surface is not etched. As for the degreasing process, for example, wet degreasing or dry degreasing can be used, but from the viewpoint of simplifying the manufacturing process, dry degreasing is preferred.

[0370] The dry degreasing process described above is the same as that described in the energy storage device of aspect 4. The wet degreasing process described above is the same as that described in the energy storage device of aspect 4. The thickness of the metal foil layer is the same as that described in the energy storage device of aspect 4.

[0371] [Manufacturing methods for encapsulation materials]

[0372] In the manufacturing method of the packaging material involved in aspect 5 and the manufacturing method of the packaging material involved in aspect 4, steps S12 and S13 are different.

[0373] <Process S12>

[0374] In step S12, using the adhesive that forms the first adhesive layer 12, the surface of the anti-corrosion treatment layer 14a opposite to the metal foil layer is bonded to the substrate layer 11 by methods such as dry lamination. In step S12, a heat treatment can be performed to promote the adhesion of the first adhesive layer 12. There are no particular limitations on the temperature during the heat treatment, but it can be, for example, 40 to 120°C.

[0375] <Process S13>

[0376] After step S12, using the adhesive constituting the second adhesive layer 17, the surface of the anti-corrosion treatment layer 14b, which consists of the substrate layer 11, the first adhesive layer 12, the anti-corrosion treatment layer 14a, the metal foil layer, and the anti-corrosion treatment layer 14b stacked sequentially, is bonded to the sealant layer 16 using a dry lamination method or similar method. In step S13, a heat treatment can be performed to promote the adhesion of the second adhesive layer 17. There are no particular limitations on the temperature during the heat treatment; for example, it can be 40–120°C.

[0377] [Electronic Storage Devices]

[0378] The encapsulation material 25 has excellent deep-drawing formability, and is therefore suitable for all-solid-state batteries in which a recess is formed by cold forming and the battery contents are housed within the recess.

[0379] Example

[0380] The present disclosure will now be described in more detail based on the embodiments, but the present disclosure is not limited to the following embodiments.

[0381] Study 1

[0382] [Materials Used]

[0383] The materials used in the examples and comparative examples are shown below.

[0384] <Substrate layer (25μm thick)>

[0385] Ny: A nylon (Ny) film (manufactured by Toyobo Co., Ltd.) with a surface corona treated.

[0386] PET: Polyethylene terephthalate film with one surface treated with corona discharge.

[0387] <First Adhesive Layer>

[0388] The first adhesive is obtained as follows: The main agent and curing agent shown in Table 1 are mixed such that the NCO / OH ratio or epoxy group / OH ratio is as shown in the table, and diluted with ethyl acetate to a solid content of 26% by mass. When using two curing agents, they are mixed such that the proportion of NCO groups in each curing agent relative to the total NCO groups in the curing agent is as shown in Table 1. Details of the components constituting the first adhesive are described below.

[0389] (Main ingredient)

[0390] A-1: Polyester polyol (manufactured by Hitachi Chemical Company, Ltd., trade name: TESLAC 2505-63, hydroxyl value: 7-11 mgKOH / g)

[0391] A-2: Acrylic polyol (manufactured by Taisei Fine Chemical Co., Ltd., trade name: 6KW-700, hydroxyl value: 10mgKOH / g)

[0392] (Curing agent)

[0393] B-1: Isocyanurate form of isophorone diisocyanate (manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE 600)

[0394] B-2: Additive of toluene diisocyanate (manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE500)

[0395] B-3: Additive of hexamethylene diisocyanate (manufactured by Asahi Kasei Corporation, trade name: DURANATE P301-75E)

[0396] B-4: Epoxy resin (manufactured by ADEKA Corporation, trade name: ADEKA RESIN EP4100)

[0397] <First anti-corrosion treatment layer (substrate layer side) and second anti-corrosion treatment layer (sealant layer side)>

[0398] (CL-1): A "sodium polyphosphate stabilized cerium oxide sol" using distilled water as a solvent and with a solid component concentration adjusted to 10% by mass. It should be noted that the sodium polyphosphate stabilized cerium oxide sol is obtained by mixing 10 parts by mass of sodium salt of phosphoric acid with 100 parts by mass of cerium oxide.

[0399] (CL-2): A composition using distilled water as a solvent, consisting of 90% by mass of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corp.)".

[0400] <Barrier layer (40μm thick)>

[0401] Soft aluminum foil (manufactured by Toyo Aluminum KK, "8079 material") that has undergone annealing and degreasing treatment was used.

[0402] <Second adhesive layer (coating amount 3g / m) 2 >

[0403] A polyurethane-based adhesive was used, which was obtained by mixing polyisocyanate into an acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane.

[0404] <Sealant layer (80μm thick)>

[0405] A polyolefin film (a film whose surface on the second adhesive layer side of an unstretched polypropylene film has been corona-treated) is used.

[0406] [Production of Encapsulation Materials]

[0407] (Example A-1)

[0408] The barrier layer is bonded to the substrate layer using a first adhesive (first adhesive layer) via dry lamination. The lamination of the barrier layer and the substrate layer is performed as follows: the first adhesive is applied to one surface of the barrier layer in such a manner that the dried coating amount (mass per unit area) is the value shown in Table 1, dried at 80°C for 1 minute, then laminated with the substrate layer, and aged at 80°C for 120 hours.

[0409] Next, using a dry lamination method, a polyurethane-based adhesive (second adhesive layer) is used to bond the surface of the barrier layer opposite to the substrate layer to the sealant layer (80 μm thick). The lamination of the barrier layer and the sealant layer is performed such that the dried coating weight (mass per unit area) is 3 g / m². 2A polyurethane adhesive was applied to the surface of the barrier layer opposite to the substrate layer, dried at 80°C for 1 minute, then laminated with the sealant layer, and aged at 120°C for 3 hours. Using this method, an encapsulation material (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was fabricated.

[0410] (Examples A-2 to A-16)

[0411] As shown in Table 1, at least one of the composition of the first adhesive and the coating amount of the first adhesive were changed. Otherwise, the encapsulation materials (layers of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of Examples A-2 to A-16 were prepared in the same manner as in Example A-1.

[0412] (Example A-17)

[0413] First, apply the first and second anti-corrosion treatment layers to the barrier layer according to the following steps. Specifically, use microgravure coating to achieve a dry coating weight of 70 mg / m². 2 (CL-1) was coated onto both sides of the barrier layer using a specific method, and then fired at 200°C in a drying unit. Next, microgravure coating was used to achieve a dry coating weight of 20 mg / m². 2 (CL-2) is applied onto the resulting layer in a manner that forms a composite layer consisting of (CL-1) and (CL-2) as the first and second anti-corrosion treatment layers. This composite layer, composed of (CL-1) and (CL-2), exhibits anti-corrosion properties.

[0414] Next, using a dry lamination method and a first adhesive (first adhesive layer), the first anti-corrosion layer side of the barrier layer, which contains the first and second anti-corrosion treatment layers, is bonded to the substrate layer. Then, using a dry lamination method and a polyurethane-based adhesive (second adhesive layer), the second anti-corrosion layer side of the barrier layer, which contains the first and second anti-corrosion treatment layers, is bonded to the sealant layer (80 μm thick). The lamination conditions between the barrier layer and the substrate layer, and between the barrier layer and the sealant layer, are the same as in Example A-1. An encapsulation material (a laminate of substrate layer / first adhesive layer / first anti-corrosion treatment layer / barrier layer / second anti-corrosion treatment layer / second adhesive layer / sealant layer) was fabricated using the above method.

[0415] (Example A-18)

[0416] Except for changing the substrate layer to PET, the encapsulation material (a laminate of substrate layer / first adhesive layer / first anti-corrosion treatment layer / barrier layer / second anti-corrosion treatment layer / second adhesive layer / sealant layer) of Example A-18 was made in the same manner as Example A-17.

[0417] (Comparative Examples A-1 to A-5)

[0418] As shown in Table 1, the composition of the first adhesive was changed. Otherwise, the encapsulation materials (layers of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of comparative examples A-1 to A-5 were prepared in the same manner as in example A-1.

[0419] [Determination of lamination strength]

[0420] (Lamination strength at room temperature)

[0421] The lamination strength between the barrier layer and the substrate layer of a 15mm wide encapsulation material was determined at room temperature (25°C) using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50mm / min via a 90° peel test. Furthermore, based on the obtained lamination strength, the results were evaluated according to the following criteria. The results are shown in Table 2.

[0422] A: Lamination strength is 6.0 N / 15 mm or higher.

[0423] B: Lamination strength is 4.5 N / 15 mm or higher and less than 6.0 N / 15 mm.

[0424] C: Lamination strength is 3.0 N / 15 mm or higher and less than 4.5 N / 15 mm.

[0425] D: Lamination strength less than 3.0 N / 15 mm

[0426] (Laminating strength under high temperature conditions)

[0427] Encapsulation material cut into 15mm wide pieces was placed in a high-temperature environment of 150°C for 5 minutes. Then, using a tensile testing machine (manufactured by Shimadzu Corporation), the lamination strength between the barrier layer and the substrate layer of the encapsulation material was determined by a 90-degree peel test at 150°C under tensile speed of 50mm / min. Furthermore, based on the obtained lamination strength, it was evaluated according to the following criteria. The results are shown in Table 2.

[0428] A: Lamination strength is 3.5N / 15mm or higher.

[0429] B: Lamination strength is 2.5 N / 15 mm or higher but less than 3.5 N / 15 mm.

[0430] C: Lamination strength is 2.0 N / 15 mm or higher and less than 2.5 N / 15 mm.

[0431] D: Lamination strength less than 2.0 N / 15 mm

[0432] [Evaluation of Deep Drawing Formability]

[0433] For the packaging material, the forming depth of deep drawing was evaluated using the following method. The forming depth of the forming apparatus was set in increments of 0.25 mm, ranging from 1.00 to 5.00 mm, to perform deep drawing on the packaging material. For the deep-drawn samples, the presence of cracks and pinholes was visually checked while the samples were illuminated, and the maximum forming depth that could be deep-drawn without cracks or pinholes was determined. Furthermore, the forming depth was evaluated according to the following criteria. The results are shown in Table 2.

[0434] A: The maximum forming depth is 4.00mm or more.

[0435] B: The maximum forming depth is 3.50mm or more and less than 4.00mm.

[0436] C: The maximum forming depth is 3.00mm or more and less than 3.50mm.

[0437] D: The maximum forming depth is less than 3.00mm.

[0438] [Environmental Reliability Evaluation]

[0439] For the deep-drawing formability evaluation above, samples with a forming depth of 2.00 mm (5 test samples for each sample) were stored at 150°C for one week. Then, the delamination between the substrate layer and the barrier layer was investigated by visual inspection while illuminating the area near the formed protrusion of the sample. In addition, environmental reliability was evaluated according to the following criteria. The results are shown in Table 2.

[0440] A: No stratification occurred in any of the five test samples.

[0441] D: More than one of the five test samples showed stratification.

[0442] [Table 1]

[0443]

[0444] [Table 2]

[0445]

[0446] Study 2

[0447] [Materials Used]

[0448] The materials used in the examples and comparative examples are shown below.

[0449] <Substrate layer (25μm thick)>

[0450] Ny: A nylon (Ny) film (manufactured by Toyobo Co., Ltd.) with a surface corona treated.

[0451] PET: Polyethylene terephthalate film with one surface treated with corona discharge.

[0452] <First Adhesive Layer>

[0453] The first adhesive is obtained as follows: The main agent and curing agent shown in Table 3 are mixed such that the NCO / OH ratio is as shown in the table, and diluted with ethyl acetate to a solid content of 26% by mass. When using two curing agents, they are mixed such that the proportion of NCO groups in each curing agent relative to the total NCO groups in the curing agent is as shown in Table 3. Details of the components constituting the first adhesive are described below.

[0454] (Main ingredient)

[0455] • Polyether polyol (manufactured by AGC, trade name: EXCENOL, product number: 837, hydroxyl value: 27 mg KOH / g)

[0456] • Polyester polyol (manufactured by Hitachi Chemical Company, Ltd., trade name: TESLAC 2505-63, hydroxyl value: 7~11mgKOH / g)

[0457] • Acrylic polyol (manufactured by Taisei Fine Chemical Co., Ltd., trade name: 6KW-700, hydroxyl value: 10mgKOH / g)

[0458] • Polycarbonate diol (PCD) (manufactured by Asahi Kasei Corp., trade name: DURANOL T5651, hydroxyl value: 113 mg KOH / g)

[0459] (Curing agent)

[0460] •IPDI-n: Isocyanurate form of isophorone diisocyanate (manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE 600)

[0461] • HDI-a: Additive of hexamethylene diisocyanate (manufactured by Asahi Kasei Corp., trade name: DURANATE P301-75E)

[0462] • MDI polymer: Polymer of diphenylmethane diisocyanate (manufactured by Tosoh Corporation, trade name: CORONATE 139)

[0463] • TDI-a: An adduct of toluene diisocyanate (manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE 500)

[0464] <First Anti-corrosion Treatment Layer (Substrate Layer Side) and Second Anti-corrosion Treatment Layer (Sealant Layer Side)> (CL-1): A "sodium polyphosphate stabilized cerium oxide sol" using distilled water as a solvent and with a solid content concentration adjusted to 10% by mass. It should be noted that the sodium polyphosphate stabilized cerium oxide sol is obtained by mixing 10 parts by mass of sodium salt of phosphoric acid with 100 parts by mass of cerium oxide. (CL-2): A composition using distilled water as a solvent, consisting of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" with a solid content concentration adjusted to 5% by mass of 90% by mass and "polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corp.)" with a solid content concentration adjusted to 10% by mass.

[0465] <Barrier layer (40μm thick)>

[0466] Use either annealed and degreased soft aluminum foil (manufactured by Toyo Aluminum KK, “8079 material”) or copper foil (manufactured by JX Nippon Mining & Metals Corporation, model: HA).

[0467] <Second adhesive layer (coating amount 3g / m) 2 >

[0468] Polyurethane adhesives are obtained by mixing polyisocyanates with acid-modified polyolefins dissolved in a mixed solvent of toluene and methylcyclohexane.

[0469] <Sealant layer (80μm thick)>

[0470] A polyolefin membrane (a membrane whose surface on the second adhesive layer side of an unstretched polypropylene membrane has been corona-treated) was used.

[0471] [Production of Encapsulation Materials]

[0472] (Example B-1)

[0473] The barrier layer (aluminum foil) is bonded to the substrate layer (nylon) using a first adhesive (first adhesive layer) via dry lamination. The lamination of the barrier layer and the substrate layer is performed as follows: the first adhesive is applied to one surface of the barrier layer in such a manner that the dried coating amount (mass per unit area) is the value shown in Table 3, dried at 80°C for 1 minute, then laminated with the substrate layer, and aged at 80°C for 120 hours.

[0474] Next, using a dry lamination method and a polyurethane-based adhesive (second adhesive layer), the surface of the barrier layer opposite to the substrate layer is bonded to the sealant layer (80 μm thick). The lamination of the barrier layer and the sealant layer is performed such that the dried coating weight (mass per unit area) is 3 g / m². 2 A polyurethane adhesive was applied to the surface of the barrier layer opposite to the substrate layer, dried at 80°C for 1 minute, then laminated with the sealant layer, and aged at 120°C for 3 hours. Using this method, an encapsulation material (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was fabricated.

[0475] (Examples B-2 to B-17)

[0476] As shown in Table 3, at least one of the composition of the first adhesive and the coating amount of the first adhesive were changed. Otherwise, the encapsulation materials (layers of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of Examples B-2 to B-17 were made in the same manner as in Example B-1.

[0477] (Example B-18)

[0478] The barrier layer was made of copper foil (Cu). The composition and coating amount of the first adhesive were changed as shown in Table 3. Otherwise, the encapsulation material (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of Example B-18 was made in the same way as Example B-1.

[0479] (Examples B-19 to B-21)

[0480] The barrier layer was made of aluminum foil, and its thickness was changed as shown in Table 3. Otherwise, the encapsulation materials (layers of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of Examples B-19 to B-21 were made in the same manner as in Example B-18.

[0481] (Example B-22)

[0482] Except for the absence of an anti-corrosion layer on the barrier layer, the encapsulation material (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of Example B-22 was manufactured in the same manner as Example B-16.

[0483] (Example B-23)

[0484] Except that the substrate is PET, the encapsulation material of Example B-23 (a laminate of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) was made in the same manner as Example B-16.

[0485] (Comparative Examples B-1 and B-2)

[0486] As shown in Table 3, the composition of the first adhesive was changed. Otherwise, the encapsulation materials (layers of substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer) of comparative examples B-1 and B-2 were prepared in the same manner as in example B-1.

[0487] [IR Measurement]

[0488] The encapsulation material was cut to appropriate dimensions, and peeling was performed between the substrate layer and the barrier layer, starting from the end. Attenuated total reflection (ATR) was measured using Fourier transform infrared (FT-IR) spectroscopy on the surface with more adhesive layer remaining between the substrate and barrier layers. The transmittance T0 of the infrared wavenumber at the baseline and at 2200 cm⁻¹ were calculated. -1 Up to 2300cm -1 The minimum transmittance T1 detected within the range, and at 1670 cm⁻¹ -1 Up to 1710cm -1 The minimum transmittance T2 detected within the range.

[0489] The calculated values ​​were evaluated to determine whether they satisfied the relationship 0.06 ≤ (T0-T1) / (T0-T2) ≤ 0.4. The results are shown in Table 3.

[0490] <Measurement Conditions>

[0491] Prism: Germanium

[0492] Wavenumber resolution: 4cm -1

[0493] Total number of times: 4

[0494] Baseline: Wavenumber 2500–2700 cm⁻¹ -1 The average intensity between.

[0495] <Measuring Apparatus>

[0496] Manufactured by Perkinelmer: Spectrum Spotlight 400

[0497] [Table 3]

[0498]

[0499] [Evaluation of the heat-resistant lamination strength of the outer casing]

[0500] Peeling was performed between the barrier layer and the substrate layer of the encapsulation material, cut into 15mm wide strips. The peel was measured using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50mm / min via a 90-degree peel test. It should be noted that in the following evaluations, a grade of C or higher is considered acceptable.

[0501] (Lamination strength at room temperature)

[0502] The lamination strength was measured at room temperature (25°C). Furthermore, based on the obtained lamination strength, it was evaluated according to the following criteria. The results are shown in Table 4.

[0503] A: The lamination strength is 6.0 N / 15 mm or higher.

[0504] B: The lamination strength is 4.5N / 15mm or higher and less than 6.0N / 15mm.

[0505] C: The lamination strength is 3.0 N / 15 mm or more and less than 4.5 N / 15 mm.

[0506] D: Lamination strength is less than 3.0 N / 15 mm.

[0507] (Laminating strength under high temperature conditions)

[0508] Encapsulation material cut into 15mm wide pieces was placed in a high-temperature environment of 150°C for 5 minutes. Then, the lamination strength at 150°C was measured. Furthermore, based on the obtained lamination strength, it was evaluated according to the following criteria. The results are shown in Table 4.

[0509] A: The lamination strength is 3.5N / 15mm or higher.

[0510] B: The lamination strength is above 2.5N / 15mm and less than 3.5N / 15mm.

[0511] C: The lamination strength is above 2.0 N / 15 mm and less than 2.5 N / 15 mm.

[0512] D: Lamination strength is less than 2.0 N / 15 mm.

[0513] [Evaluation of Deep Drawing Formability]

[0514] For the packaging material, the forming depth of deep-drawing was evaluated using the following method. The forming depth of the forming apparatus was set to 1.00–5.00 mm in 0.25 mm units, and the packaging material was deep-drawn. For the deep-drawn samples, the presence of cracks and pinholes was visually checked while the samples were illuminated, and the maximum forming depth of deep-drawing without cracks or pinholes was determined. Furthermore, the forming depth was evaluated according to the following criteria. The results are shown in Table 4.

[0515] A: The maximum forming depth is 5.00mm or more.

[0516] B: The maximum forming depth is 4.00mm or more and less than 5.00mm.

[0517] C: The maximum forming depth is 3.00mm or more and less than 4.00mm.

[0518] D: The maximum forming depth is less than 3.00mm.

[0519] [Evaluation of Deep Drawing Reliability]

[0520] For the deep-drawing formability evaluation above, samples with a forming depth of 2.00 mm (5 test samples for each sample) were stored at 150°C for one week. Then, while irradiating the area near the formed protrusions of the samples, the occurrence of delamination between the substrate layer and the barrier layer was visually investigated. Furthermore, environmental reliability was evaluated according to the following criteria. The results are shown in Table 4.

[0521] A: No stratification occurred in any of the five test samples.

[0522] D: More than one of the five test samples stratified.

[0523] [Table 4]

[0524]

[0525] Study 3

[0526] [Materials Used]

[0527] The materials used in the examples and comparative examples are shown below.

[0528] As the substrate layer 11, a nylon (Ny) film (manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm after one surface has been corona treated is used.

[0529] Next, five polyamide imides with different number average molecular weights (Mn) were prepared as materials constituting the first adhesive layer 12a.

[0530] The number average molecular weights (Mn) of the various polyamide imides are 2000, 5000, 20000, 30000 and 40000, respectively.

[0531] In addition, as the main agent (polyol resin) of the polyurethane-based compound constituting the first adhesive layer 12a, polyether polyol, polyester polyol, acrylic polyol, and polycarbonate polyol (PCD) are prepared. Furthermore, as the curing agent (polyfunctional isocyanate compound) of this polyurethane-based compound, hexamethylene diisocyanate adduct (HDI-a), isocyanurate isocyanate of isophorone diisocyanate (IPDI-n), and toluene diisocyanate adduct (TDI-a) are prepared.

[0532] As the barrier layer 13, a soft aluminum foil (manufactured by Toyobo Co., Ltd., "8079 material") with anti-corrosion treatment layers 14a and 14b on both sides was used. It should be noted that the anti-corrosion treatment layers 14a and 14b are formed by stabilizing cerium oxide sol with sodium polyphosphate by mixing 10 parts by mass of sodium salt of phosphoric acid with 100 parts by mass of cerium oxide.

[0533] Next, as the adhesive constituting the second adhesive layer 12b, a polyurethane-based adhesive obtained by mixing polyisocyanate in an acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane is used. It should be noted that, at 3 g / m²... 2 Apply and form the second adhesive layer 12b.

[0534] As sealant layer 16, a polyolefin film (a film whose surface on the second adhesive layer side of an unstretched polypropylene film has been corona-treated) is used. The thickness of sealant layer 16 is 80 μm.

[0535] [Preparation of encapsulation material 10]

[0536] (Example C-1)

[0537] The encapsulation material 10 of this embodiment is prepared as follows. It should be noted that the number average molecular weight (Mn) of the polyamide-imide used, the mixing amount (solid content of polyamide-imide resin relative to solid content of polyurethane compound) A, and the ratio (NCO / OH) of the main agent and curing agent of the polyurethane compound and the number of isocyanate groups contained therein are shown in Table 5.

[0538] That is, the barrier layer 13 is bonded to the substrate layer 11 by dry lamination using the first adhesive (first adhesive layer) 12a. The lamination of the barrier layer 13 and the substrate layer 11 is performed by applying the first adhesive to one surface of the barrier layer 13, drying it at 80°C for 1 minute, then laminating it with the substrate layer 11, and aging it at 80°C for 120 hours.

[0539] Next, using a polyurethane-based adhesive (second adhesive layer) 12b, the surface of the barrier layer 13 opposite to the substrate layer 11 is bonded to the sealant layer (80 μm thick) 16 by dry lamination. The lamination of the barrier layer 13 and the sealant layer 16 is performed as follows: a polyurethane-based adhesive is applied to the surface of the barrier layer 13 opposite to the substrate layer 11, dried at 80°C for 1 minute, then laminated with the sealant layer, and aged at 120°C for 3 hours. Using the above method, an encapsulation material (a laminate of substrate layer 11 / first adhesive layer 12a / barrier layer 13 / second adhesive layer 12b / sealant layer 16) 10 is produced.

[0540] (Comparative Examples C-1 to C-4)

[0541] Comparative Examples C-1 to C-4 were compared with Example C-1, which contained polyamide-imide, to investigate the effect of the presence or absence of polyamide-imide. The number-average molecular weight (Mn) and mixing amount A of the polyamide-imide used in each comparative example, as well as the main agent and curing agent of the polyurethane compound and the NCO / OH ratio, are shown in Table 5.

[0542] (Examples C-2 to C-5)

[0543] The effect of the mixing amount A of polyamide-imide was investigated by comparing these examples with Example C-1. The number-average molecular weight (Mn) of polyamide-imide, the mixing amount A, and the main agent and curing agent of the polyurethane compound, as well as the NCO / OH ratio, are shown in Table 5.

[0544] (Examples C-6 to C-9)

[0545] The effect of the number-average molecular weight (Mn) of polyamide-imide was investigated by comparing these examples with Example C-1. The number-average molecular weight (Mn) of polyamide-imide, the mixing amount A, and the main agent and curing agent of the polyurethane compound, as well as the NCO / OH ratio, are shown in Table 5.

[0546] (Examples C-10 to C-12)

[0547] The influence of the type of main agent in polyurethane compounds was investigated by comparing these examples with Example C-1. The number-average molecular weight (Mn) and mixing amount A of polyamide-imide, as well as the main agent and curing agent of the polyurethane compounds and the NCO / OH ratio, are shown in Table 5.

[0548] (Examples C-13 to C-14)

[0549] The effect of the type of curing agent on the polyurethane compounds was investigated by comparing these examples with Example C-1. The number-average molecular weight (Mn) and mixing amount A of the polyamide-imide, as well as the main agent and curing agent of the polyurethane compounds and the NCO / OH ratio, are shown in Table 5.

[0550] (Examples C-15 to C-19)

[0551] The effect of NCO / OH on the polyurethane compounds was investigated by comparing these examples with Example C-1. The number-average molecular weight (Mn) and mixing amount A of the polyamide-imide, as well as the main agent and curing agent of the polyurethane compounds and the NCO / OH ratio, are shown in Table 5.

[0552] [Evaluation of Packaging Material 10]

[0553] The encapsulation material 10 produced in each embodiment and comparative example was evaluated from four perspectives: evaluation of lamination strength at room temperature, evaluation of lamination strength at high temperature (170°C), evaluation of deep-drawing formability, and evaluation of the reliability (molding reliability) of the molded encapsulation material 10 at high temperature (170°C).

[0554] (Determination of lamination strength at room temperature)

[0555] The lamination strength between the barrier layer and the substrate layer of the encapsulation material cut into 15 mm wide sections at room temperature (25°C) was determined by a 90-degree peel test using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min. Furthermore, based on the obtained lamination strength, the results were evaluated according to the following criteria. The results are shown in Table 5.

[0556] A: The lamination strength is 6.0 N / 15 mm or higher.

[0557] B: The lamination strength is 4.5N / 15mm or higher and less than 6.0N / 15mm.

[0558] C: The lamination strength is 3.0 N / 15 mm or more and less than 4.5 N / 15 mm.

[0559] D: Lamination strength is less than 3.0 N / 15 mm.

[0560] (Determination of lamination strength under high temperature conditions)

[0561] Encapsulation material cut into 15mm wide pieces was placed in a high-temperature environment of 170°C for 5 minutes. Then, the lamination strength between the barrier layer and the substrate layer of the encapsulation material at 150°C was determined using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50mm / min via a 90-degree peel test. Furthermore, based on the obtained lamination strength, the results were evaluated according to the following criteria. The results are shown in Table 5.

[0562] A: The lamination strength is 3.0N / 15mm or higher.

[0563] B: The lamination strength is above 2.0N / 15mm and less than 3.0N / 15mm.

[0564] C: The lamination strength is 1.0 N / 15 mm or more and less than 2.0 N / 15 mm.

[0565] D: Lamination strength is less than 1.0 N / 15 mm.

[0566] (Evaluation of deep-drawing formability)

[0567] For the packaging material, the forming depth that can be deep-drawn was evaluated using the following method. The forming depth of the forming apparatus was set in increments of 0.25 mm, ranging from 1.00 to 5.00 mm, and the packaging material was deep-drawn. For the deep-drawn samples, the presence of cracks and pinholes was visually checked while the samples were illuminated, and the maximum forming depth that could be deep-drawn without cracks or pinholes was determined. Furthermore, the forming depth was evaluated according to the following criteria. The results are shown in Table 5.

[0568] A: The maximum forming depth is 4.00mm or more.

[0569] B: The maximum forming depth is 3.50mm or more and less than 4.00mm.

[0570] C: The maximum forming depth is 3.00mm or more and less than 3.50mm.

[0571] D: The maximum forming depth is less than 3.00mm.

[0572] (Evaluation of molding reliability)

[0573] For the deep-drawing formability evaluation above, samples with a forming depth of 2.00 mm (5 test samples for each sample) were stored at 170°C for one week. Then, while irradiating the area near the formed protrusion of the sample, the occurrence of delamination between the substrate layer and the barrier layer was investigated by visual inspection. As a measure of forming reliability, the following criteria were used for evaluation. The results are shown in Table 5.

[0574] A: The number of stratified cases was 0 out of 5 tested samples.

[0575] B: The number of stratified occurrences was 1 to 2 out of 5 tested samples.

[0576] C: The number of stratification occurrences is more than 3 out of 5 tested samples.

[0577]

[0578] [discuss]

[0579] (Discussion on the effect of the presence or absence of mixed polyamide-imide)

[0580] The results from Examples C-1 and Comparative Examples C-1 to C-4 show that while no significant difference was observed in the lamination strength at room temperature due to the presence or absence of polyamide-imide, the lamination strength and deep-drawing formability at high temperatures were significantly improved by mixing with polyamide-imide. Furthermore, the reliability (molding reliability) of the molded encapsulation material 10 at high temperatures was also consistent.

[0581] It should be noted that the polyurethane compound composed of the reaction product of polyester polyol and IPDI-n has relatively high heat resistance. However, compared with comparative examples C-3 and C-4, which used this polyurethane compound, Example C-1, which contains polyamide-imide, exhibits superior lamination strength and molding reliability at high temperatures. Furthermore, although the NCO / OH ratio was increased in comparative example C-4 to further improve heat resistance, Example C-1 is superior.

[0582] (Discussion regarding the mixing amount A of polyamide-imide)

[0583] Based on the results of Examples C-1 to C-4, it can be understood that the higher the mixing amount of polyamide-imide (the solid content of the polyamide-imide resin relative to the solid content of the polyurethane compound) A, the higher the lamination strength and molding reliability at high temperatures. However, in Example C-5, where the mixing amount A reached 20.0% by mass, the lamination strength at high temperatures was low and the deep-drawing formability was significantly reduced compared to Examples C-1 to C-4, where the mixing amount A was 15.0% by mass or less.

[0584] Therefore, to balance lamination strength and molding reliability under high-temperature conditions, the mixing amount A of polyamide-imide should be 1.0% by mass < A < 20.0% by mass. The optimal lamination strength under high-temperature conditions is 10.0–15.0% by mass.

[0585] (Discussion on the number-average molecular weight (Mn) of polyamide-imide)

[0586] Based on the results of Examples C-1, C-6 to C-9, it can be understood that when the number-average molecular weight (Mn) of the polyamide-imide resin satisfies 3000 < Mn < 36000 (Examples C-6 to C-8), the lamination strength under high-temperature conditions is excellent, especially within this range where the lower the number-average molecular weight (Mn), the better. The reason for this is not yet clear, but it is speculated, for example, that it is related to the following: in low molecular weight polyamide-imide resins, the number of functional groups per unit mass is greater, thus resulting in excellent interfacial adhesion.

[0587] It should be noted that when the number-average molecular weight (Mn) is less than 5000 (Example C-1), the lamination strength at high temperatures is lower compared to cases with a larger number (Examples C-6 to C-9). This is presumably related to the following: when the number-average molecular weight (Mn) is less than 5000, as the number of functional groups per unit mass increases, the brittleness of the polyamide-imide increases, and its melting point, glass transition temperature, or softening point decreases, thereby reducing its heat resistance.

[0588] It should be noted that when the number average molecular weight (Mn) of the polyamide-imide is greater than 36,000 (Example C-9), this high molecular weight polyamide-imide cannot be dissolved in a solvent, and therefore the substance mixed with this high molecular weight polyamide-imide cannot be used as an adhesive.

[0589] (Discussion on the types of main agents in polyurethane compounds)

[0590] Based on the results of Examples C-1, C-10 to C-12, it can be understood that, compared to the case where polyether polyols are used as the main agent (polyol resin) of the polyurethane compound (Example C-1), the use of polyol resins selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate polyols (PCD) (Examples C-10 to C-12) exhibits superior lamination strength at high temperatures. Among these, the use of polyester polyols (Example C-10) demonstrates superior lamination strength at high temperatures compared to the use of acrylic polyols and PCD (Examples C-11 and C-12). It should also be noted that deep-drawing formability and molding reliability are also excellent.

[0591] (Discussion on the types of curing agents for polyurethane compounds)

[0592] Based on the results of Examples C-1, C-13, and C-14, it can be understood that, compared to the case where aliphatic HDI-a is used as the curing agent (polyfunctional isocyanate compound) for the polyurethane compound (Example C-1), the lamination strength at high temperatures is superior when using alicyclic IPDI-n or TDI-a containing aromatic rings in the molecular structure (Examples C-13 and C-14). Furthermore, deep-drawing formability and molding reliability are also excellent.

[0593] (Discussion on NCO / OH in polyurethane compounds)

[0594] Based on the results of Examples C-1, C-15 to C-19, it can be understood that if the NCO / OH ratio of the polyurethane compound satisfies 1.5 < NCO / OH < 40.0 (Examples C-1, C-15 to C-19), the lamination strength, deep drawing formability, and molding reliability under high-temperature conditions can all be improved. In particular, when the NCO / OH ratio is 10.0 to 30.0 (Examples C-16 to C-18), both the lamination strength and deep drawing formability under high-temperature conditions are excellent.

[0595] Study 4

[0596] [Materials Used]

[0597] The materials used in the examples and comparative examples are shown below.

[0598] <Substrate layer (25μm thick)>

[0599] A polyethylene terephthalate film with a surface that has been corona-treated was used.

[0600] <First adhesive layer (4μm thick) and second adhesive layer (3μm thick)>

[0601] The adhesive is prepared by mixing the main agent, curing agent, and hydrogen sulfide adsorbent listed in Table 6 in the proportions shown in Table 7. Details of the main agent and curing agent shown in Tables 6 and 7 are described below. Furthermore, the hydrogen sulfide adsorbent uses the following compound.

[0602] {Main Agent}

[0603] • Amine resin (manufactured by Nippon Shokubai Co., Ltd., trade name: POLYMENT MK-380)

[0604] • Epoxy resin (manufactured by Arakawa Chemical Industries, Ltd., trade name: ARAKYD9201N)

[0605] • Polyester polyol resin (manufactured by UNITIKA LTD., trade name: ELITEL UE-3600)

[0606] {Curing agent}

[0607] HDI-B (Hexamethylene diisocyanate-biuret, manufactured by Asahi Kasei Corp., trade name: DURANATE 24A-100)

[0608] HDI-N1 (Hexamethylene diisocyanate-isocyanurate, manufactured by Asahi Kasei Corp., trade name: DURANATE TPA-100)

[0609] HDI-N2 (a compound formed by combining the isocyanate group of hexamethylene diisocyanate-isocyanurate with a capping agent, manufactured by Asahi Kasei Corp., trade name: DURANATE MF-K60B)

[0610] HDI-N3 (a compound formed by combining the isocyanate group of hexamethylene diisocyanate-isocyanurate with a capping agent, manufactured by Asahi Kasei Corp., trade name: DURANATE MF-B60B)

[0611] HDI-A (Hexamethylene diisocyanate adduct, manufactured by TOYOINK CO.,LTD., trade name: CAT-10L)

[0612] Bisphenol A (manufactured by Mitsubishi Chemical Corporation, trade name: Bisphenol A)

[0613] {Hydrogen sulfide adsorbent}

[0614] Zinc oxide (manufactured by ISHIHARA SANGYO KAISHA,LTD., trade name: FZO-50)

[0615] <Anti-corrosion treatment layer>

[0616] A "sodium polyphosphate stabilized cerium oxide sol" was prepared using distilled water as a solvent and with a solid component concentration adjusted to 10% by mass. It should be noted that the sodium polyphosphate stabilized cerium oxide sol was obtained by mixing 10 parts by mass of sodium phosphate with 100 parts by mass of cerium oxide.

[0617] <Barrier layer (35μm thick)>

[0618] Soft aluminum foil (manufactured by Toyo Aluminum KK, "8079 material") that has undergone annealing and degreasing treatment was used.

[0619] <Sealant layer (40μm thick)>

[0620] As a sealant layer, the membrane described in Table 6 was prepared.

[0621] [Manufacturing of encapsulation materials]

[0622] <Examples D-1 to D-3, D-9 to D-12, Comparative Examples D-1 and D-2>

[0623] The barrier layer is bonded to the substrate layer using an adhesive (first adhesive layer) via dry lamination. Then, the sealant layer is bonded to the surface of the barrier layer opposite to the surface bonded to the first adhesive layer using an adhesive (second adhesive layer) via dry lamination.

[0624] The laminate thus obtained was heat-treated under the conditions shown in Table 7 to manufacture the encapsulation material (substrate layer / first adhesive layer / barrier layer / second adhesive layer / sealant layer).

[0625] <Examples D-4 to D-8>

[0626] First, sodium polyphosphate stabilized cerium oxide sol is applied to both sides of the barrier layer using gravure coating. Next, after drying the applied sodium polyphosphate stabilized cerium oxide sol, it is sequentially fired to form an anti-corrosion treatment layer on both sides of the barrier layer. The firing conditions are set at 150°C and for 30 seconds.

[0627] Next, using a dry lamination method and an adhesive (first adhesive layer), the substrate layer is bonded to one side of the barrier layer where the anti-corrosion treatment layer is formed. Then, using a dry lamination method and a (second adhesive layer), the sealant layer is bonded to the other side of the barrier layer where the anti-corrosion treatment layer is formed.

[0628] Under the conditions shown in Table 7, the laminate thus obtained was subjected to heat treatment to manufacture an encapsulation material (substrate layer / first adhesive layer / anti-corrosion treatment layer / barrier layer / anti-corrosion treatment layer / second adhesive layer / sealant layer).

[0629] [Determination of urea abundance ratio]

[0630] <First adhesive layer>

[0631] The barrier layer and substrate layer, which are tightly bonded to the first adhesive layer, are peeled off to expose the first adhesive layer. The intensity of the infrared absorption spectrum peak of the exposed first adhesive layer is measured using infrared spectroscopy (IR). The intensity of the peak value is between 1680 and 1720 cm⁻¹. -1 The infrared absorption spectrum peak intensity was set to A1, 1590–1640 cm⁻¹. -1 When the infrared absorption spectrum peak intensity is set to B1, the urea abundance ratio (X1) is calculated using the following formula (2-A). The results are shown in Table 6.

[0632] Urea abundance ratio (X1) = {B1 / (A1+B1)} × 100 …(2-A)

[0633] <Second adhesive layer>

[0634] The barrier layer and sealant layer, which were tightly bonded to the second adhesive layer, were peeled off to expose the second adhesive layer. The urea abundance ratio was calculated for the exposed second adhesive layer in the same manner as for the first adhesive layer. The results are shown in Table 6.

[0635] [Evaluation of the heat-resistant lamination strength of the sealant layer]

[0636] <Determination Method>

[0637] Cut the encapsulation material into 15mm wide pieces and determine the lamination strength between the barrier layer and the sealant layer of the encapsulation material under any of the following conditions 1 to 3. Peeling is performed at 90° and the peeling speed is 50mm / min.

[0638] Condition 1: Heat the encapsulation material at 80°C for 5 minutes, and then measure the lamination strength while heating at 80°C.

[0639] Condition 2: Heat the encapsulation material at 150°C for 5 minutes, and then measure the lamination strength while heating at 150°C.

[0640] Condition 3: The encapsulation material is heated at 100°C and exposed to hydrogen sulfide at a concentration of 20 ppm for 1 week, and then the lamination strength is determined using the same method as in Condition 2 above.

[0641] <Evaluation Criteria>

[0642] The lamination strength was evaluated based on the following criteria, with a value of C or higher considered acceptable. The results are shown in Table 8.

[0643] A: Lamination strength is 2.5N / 15mm or higher.

[0644] B: Lamination strength is 2.0 N / 15 mm or higher and less than 2.5 N / 15 mm.

[0645] C: Lamination strength is ≥1.5N / 15mm and <2.0N / 15mm

[0646] D: Lamination strength less than 1.5 N / 15 mm

[0647] [Deep drawing formability]

[0648] <Determination Method>

[0649] For the packaging materials obtained in each example, the forming depth that can be deep-drawn was evaluated using the following method. The forming depth of the forming apparatus was set in increments of 0.25 mm, ranging from 1.00 to 5.00 mm. For the deep-drawn samples, the presence of cracks and pinholes was visually checked while the packaging material was illuminated. The maximum forming depth that could be deep-drawn without cracks or pinholes was determined. Furthermore, the forming depth was evaluated according to the following criteria. The results are shown in Table 8.

[0650] <Evaluation Criteria>

[0651] A: The maximum forming depth is 4.00mm or more.

[0652] B: The maximum forming depth is 3.50mm or more and less than 4.00mm.

[0653] C: The maximum forming depth is 3.00mm or more and less than 3.50mm.

[0654] D: The maximum forming depth is less than 3.00mm.

[0655] [Heat resistance after deep drawing]

[0656] The packaging material with a forming depth of 2.00 mm obtained in the above evaluation of [deep drawing formability] (5 test samples for each sample) was heated to 80°C or 150°C and stored for 1 week. Then, while irradiating the vicinity of the formed protrusion, the occurrence of delamination between the substrate layer and the barrier layer was visually confirmed. For this test, the evaluation was carried out according to the following criteria. The results are shown in Table 8.

[0657] <Evaluation Criteria>

[0658] A: Stratification occurred in 0 to 1 of the 5 test samples.

[0659] B: Stratification occurred in 2 to 4 out of 5 test samples.

[0660] D: Stratification occurred in 5 out of 5 test samples.

[0661] [Applicable Period]

[0662] The pot life was evaluated based on the gel fraction of the adhesive coating at predetermined time intervals. The gel fraction was determined using the following method. The gel fraction was evaluated based on the following criteria. The results are shown in Table 8.

[0663] <Gel fraction determination>

[0664] Step A) After preparing the adhesive coating solution, a portion of the coating solution is recovered after 4 hours, and the solvent of the coating solution is dried.

[0665] Step B) Measure the weight of the sieve on which the sample is placed (let w1), and measure the total weight of the dried coating from Step A placed on the sieve (let w2).

[0666] Step C) Immerse the dried coating from Step A in xylene and store it at room temperature for 1 week.

[0667] Step D) Filter the xylene solution from step C using the sieve used in step B, and wash the residue with a large amount of xylene.

[0668] Step E) Dry the residue from step D and measure its weight (let w3).

[0669] Step F) Based on the weight data obtained above, calculate the gel fraction using the following formula.

[0670] Gel fraction = (w3-w1) / (w2-w1)

[0671] <Evaluation Criteria>

[0672] A: Gel fraction less than 40%

[0673] B: Gel fraction is 40% or more but less than 50%.

[0674] C: Gel fraction is 50% or more but less than 60%.

[0675] D: Gel fraction of 60% or more

[0676] [Resistance to molding and curling]

[0677] The encapsulation material with a forming depth of 2.00 mm obtained in the above evaluation of [deep drawing formability] was placed on a flat surface. The encapsulation material was placed in such a way that the surface with the recessed portion was in contact with the flat surface. For the placed encapsulation material, the curl height of the four corners of the encapsulation material from the flat surface was measured, and their total value was calculated. The total value was evaluated based on the following evaluation criteria. The results are shown in Table 8.

[0678] <Evaluation Criteria>

[0679] A: The total curling height of the four corners is less than 40mm.

[0680] B: The total curling height of the four corners is 40mm or more but less than 100mm.

[0681] D: The total curling height of the four corners is 100mm or more.

[0682] [Heat-sealing strength]

[0683] A 120mm × 60mm piece of encapsulation material was cut and folded in half with the sealant layer facing inwards. The end opposite the folded portion was heat-sealed for 10mm at 190°C / 0.5MPa / 3 seconds and stored at room temperature for 6 hours. Then, a sample for heat seal strength testing was prepared by cutting the central portion of the heat-sealed section in the longitudinal direction, with a width of 15mm × a length of 300mm. This sample was placed in a test environment at 150°C for 5 minutes, and then a T-peel test was performed on the heat-sealed section of the sample using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50mm / min. The heat seal strength was then evaluated based on the following criteria. The results are shown in Table 8.

[0684] <Evaluation Criteria>

[0685] A: Heat seal strength is 15N / 15mm or higher.

[0686] B: Heat seal strength is 10N / 15mm or higher but less than 15N / 15mm

[0687] C: Heat seal strength is 5N / 15mm or higher and less than 10N / 15mm.

[0688] D: Heat seal strength less than 5N / 15mm

[0689]

[0690]

[0691]

[0692] The results of heat-resistant lamination strength measurements on the sealant layer side at 80°C and 150°C show that, compared to cases where the urea abundance ratio (X1) is less than 10 or greater than 99 (Comparative Examples D-1 to D-3), the heat resistance is excellent when the urea abundance ratio (X1) is 10 to 99 (Examples D-1 to D-12). Furthermore, the evaluation of heat resistance after deep drawing shows that, compared to cases where the urea abundance ratio (X1) is less than 10 or greater than 99 (Comparative Examples D-1 to D-3), the heat resistance is excellent when the urea abundance ratio (X1) is 10 to 99 (Examples D-1 to D-12).

[0693] Study 5

[0694] [Materials Used]

[0695] The materials used in the examples and comparative examples are shown below.

[0696] <Substrate layer (25μm thick)>

[0697] A polyethylene terephthalate film with a surface that has been corona-treated was used.

[0698] <First adhesive layer (4μm thick) and second adhesive layer (3μm thick)>

[0699] The adhesive is prepared by mixing the main agent, curing agent, catalyst, and hydrogen sulfide adsorbent listed in Table 1 in the proportions shown in Table 10. Details of the main agent and curing agent shown in Tables 9 and 10 are described below. Furthermore, the catalyst and hydrogen sulfide adsorbent use the following compounds.

[0700] {Main Agent}

[0701] • Acrylic polyol resin (manufactured by Toei Kasei Co., Ltd., trade name: YS#6158)

[0702] • Polyester polyol resin (manufactured by UNITIKA LTD., trade name: ELITEL UE-3220)

[0703] • Polyolefin resin (manufactured by Mitsui Chemicals, Inc., trade name: UNISTOLE P501)

[0704] {Curing agent}

[0705] HDI-B (Hexamethylene diisocyanate-biuret, manufactured by Asahi Kasei Corp., trade name: DURANATE 24A-100)

[0706] HDI-A (Hexamethylene diisocyanate-addition compound, manufactured by TOYOINK CO.,LTD., trade name: SP curing agent)

[0707] • TDI-A (Toluene diisocyanate - adduct, manufactured by TOYO INK CO.,LTD., trade name: CAT-10L)

[0708] • TDI-N (Toluene diisocyanate-isocyanurate, manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE D-204EA-1)

[0709] {catalyst}

[0710] • Organotitanium compound (manufactured by Matsumoto Fine Chemical Co., trade name: ORGATIX TC-401)

[0711] {Hydrogen sulfide adsorbent}

[0712] Zinc oxide (manufactured by ISHIHARA SANGYO KAISHA,LTD., trade name: FZO-50)

[0713] <Anti-corrosion treatment layer>

[0714] A "sodium polyphosphate stabilized cerium oxide sol" was prepared using distilled water as a solvent and with a solid component concentration adjusted to 10% by mass. It should be noted that the sodium polyphosphate stabilized cerium oxide sol was obtained by mixing 10 parts by mass of sodium phosphate with 100 parts by mass of cerium oxide.

[0715] <Metal foil layer (thickness 35μm)>

[0716] Soft aluminum foil (manufactured by Toyo Aluminum KK, "8079 material") that has undergone annealing and degreasing treatment was used.

[0717] <Sealant layer (40μm thick)>

[0718] As a sealant layer, the membrane described in Table 9 was prepared.

[0719] [Manufacturing of encapsulation materials]

[0720] <Examples E-1 to E-5, Comparative Examples E-1 to E-3>

[0721] The metal foil layer is bonded to the substrate layer using an adhesive (first adhesive layer) via dry lamination. Then, a sealant layer is bonded to the side of the metal foil layer opposite to the side bonded to the first adhesive layer using an adhesive (second adhesive layer) via dry lamination.

[0722] Under the conditions shown in Table 10, the resulting laminate was heat-treated to manufacture an encapsulation material (substrate layer / first adhesive layer / metal foil layer / second adhesive layer / sealant layer).

[0723] <Examples E-6 to E-11>

[0724] First, sodium polyphosphate stabilized cerium oxide sol is applied to both sides of a metal foil layer using gravure coating. Next, the applied sodium polyphosphate stabilized cerium oxide sol is dried, and then sequentially fired to form an anti-corrosion treatment layer on both sides of the metal foil layer. The firing conditions are set at 150°C and a processing time of 30 seconds.

[0725] Next, using a dry lamination method, an adhesive (first adhesive layer) is used to bond the substrate layer to one side of the metal foil layer with the anti-corrosion treatment layer formed. Then, using a dry lamination method, a sealant layer (second adhesive layer) is used to bond the sealant layer to the other side of the metal foil layer with the anti-corrosion treatment layer formed.

[0726] Under the conditions shown in Table 10, the resulting laminate was heat-treated to manufacture an encapsulation material (substrate layer / first adhesive layer / anti-corrosion treatment layer / metal foil layer / anti-corrosion treatment layer / second adhesive layer / sealant layer).

[0727] [Determination of carbamate group abundance ratio]

[0728] <First adhesive layer>

[0729] The metal foil layer and substrate layer, which are tightly bonded to the first adhesive layer, are peeled off to expose the first adhesive layer. The intensity of the infrared absorption spectrum peak of the exposed first adhesive layer is measured using infrared spectroscopy (IR). (2250–2290 cm⁻¹) -1 The infrared absorption spectrum peak intensity was set to A2, 1680–1720 cm⁻¹. -1 When the infrared absorption spectrum peak intensity is set to B2, the abundance ratio of carbamate groups (X2) is calculated using the following formula (2-B). The results are shown in Table 9.

[0730] The abundance ratio of carbamate groups (X2) = {B2 / (A2+B2)} × 100…(2-B)

[0731] <Second adhesive layer>

[0732] The metal foil layer and sealant layer that were tightly bonded to the second adhesive layer were peeled off to expose the second adhesive layer. For the exposed second adhesive layer, the urethane group abundance ratio was calculated in the same manner as for the first adhesive layer. The results are shown in Table 9.

[0733] [Determination of glass transition temperature Tg]

[0734] <First adhesive layer and second adhesive layer>

[0735] The glass transition temperatures (Tg) of the first and second adhesive layers were determined by differential scanning calorimetry (DSC) at a measurement temperature of 20–300 °C and a heating rate of 10 °C / min. The results are shown in Table 9.

[0736] [Evaluation of the heat-resistant lamination strength of the sealant layer]

[0737] <Determination Method>

[0738] Cut the encapsulation material into 15 mm wide pieces and measure the lamination strength between the metal foil layer and the sealant layer of the encapsulation material under any of the following conditions 1 to 3. Set the peel angle to 90° and the peel speed to 50 mm / min.

[0739] Condition 1: Heat the encapsulation material at 80°C for 5 minutes, and then measure the lamination strength while heating at 80°C.

[0740] Condition 2: Heat the encapsulation material at 150°C for 5 minutes, and then measure the lamination strength while heating at 150°C.

[0741] Condition 3: The encapsulation material is heated at 100°C and exposed to hydrogen sulfide at a concentration of 20 ppm for 1 week, and then the lamination strength is determined using the same method as in Condition 2 above.

[0742] <Evaluation Criteria>

[0743] The lamination strength was evaluated based on the following criteria. The results are shown in Table 11.

[0744] A: Lamination strength is 2.5N / 15mm or higher.

[0745] B: Lamination strength is 2.0 N / 15 mm or higher and less than 2.5 N / 15 mm.

[0746] C: Lamination strength is ≥1.5N / 15mm and <2.0N / 15mm

[0747] D: Lamination strength less than 1.5 N / 15 mm

[0748] [Deep drawing formability]

[0749] <Determination Method>

[0750] For the packaging materials obtained in each example, the forming depth that can be deep-drawn was evaluated using the following method. The forming depth of the forming apparatus was set to 1.0–5.0 mm in 0.25 mm increments. For the deep-drawn samples, the presence of cracks and pinholes was visually checked while the packaging material was illuminated. The maximum forming depth that could be deep-drawn without cracks or pinholes was determined. Furthermore, the forming depth was evaluated according to the following criteria, with C or above considered acceptable. The results are shown in Table 11.

[0751] <Evaluation Criteria>

[0752] A: The maximum forming depth is 4.00mm or more.

[0753] B: The maximum forming depth is 3.50mm or more and less than 4.00mm.

[0754] C: The maximum forming depth is 3.00mm or more and less than 3.50mm.

[0755] D: The maximum forming depth is less than 3.00mm.

[0756] [Heat resistance after deep drawing]

[0757] The packaging material with a forming depth of 2.00 mm obtained in the above evaluation of [deep drawing formability] (5 test samples for each sample) was heated to 80°C or 150°C and stored for 1 week. Then, while irradiating the vicinity of the formed protrusion, the occurrence of delamination between the substrate layer and the metal foil layer was visually confirmed. For this test, the evaluation was carried out according to the following criteria. The results are shown in Table 11.

[0758] <Evaluation Criteria>

[0759] A: Stratification occurred in 0 to 1 of the 5 test samples.

[0760] C: Stratification occurred in 2 to 4 out of 5 test samples.

[0761] D: Stratification occurred in 5 out of 5 test samples.

[0762] [Heat-sealing strength]

[0763] A 120mm × 60mm piece of encapsulation material was cut and folded in half with the sealant layer facing inwards. The end opposite the folded portion was heat-sealed for 10mm at 190°C / 0.5MPa / 3 seconds and stored at room temperature for 6 hours. Then, a sample for heat seal strength testing was prepared by cutting the central portion of the heat-sealed section in the longitudinal direction, with a width of 15mm × a length of 300mm. This sample was placed in a test environment at 150°C for 5 minutes, and then a T-peel test was performed on the heat-sealed section of the sample using a tensile testing machine (manufactured by Shimadzu Corporation) at a tensile speed of 50mm / min. The heat seal strength was then evaluated based on the following evaluation criteria. The results are shown in Table 11.

[0764] <Evaluation Criteria>

[0765] A: Heat seal strength is 15N / 15mm or higher.

[0766] B: Heat seal strength is 10N / 15mm or higher but less than 15N / 15mm

[0767] C: Heat seal strength is 5N / 15mm or higher and less than 10N / 15mm.

[0768] D: Heat seal strength less than 5N / 15mm

[0769]

[0770]

[0771]

[0772] Industrial applicability

[0773] According to this disclosure, an encapsulation material for an energy storage device and an energy storage device using the encapsulation material can be provided, which can ensure excellent lamination strength under both room temperature and high temperature conditions and also have excellent deep drawing formability.

[0774] Explanation of symbols

[0775] 1…battery element, 2…lead wire, 10, 20, 25…encapsulation material for energy storage device, 11…substrate layer, 12a…first adhesive layer (first adhesive layer), 12b…second adhesive layer, 13…barrier layer, 14a…first anti-corrosion treatment layer, 14b…second anti-corrosion treatment layer, 15…adhesive resin layer, 16…sealant layer, 17…second adhesive layer, 30…embossed encapsulation material, 32…molded processing area (recess), 34…cover, 40…secondary battery, 50…energy storage device, 52…battery element, 53…metal terminal.

Claims

1. An encapsulation material for an energy storage device, comprising at least a substrate layer, a barrier layer, and a sealant layer in sequence. An adhesive layer is provided between the substrate layer and the barrier layer. This adhesive layer contains a polyurethane-based compound composed of a reaction product of at least one polyester polyol resin and at least one polyfunctional isocyanate compound. The polyfunctional isocyanate compound contains the isocyanurate form of isophorone diisocyanate. Based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from the isocyanurate body of the isophorone diisocyanate in the polyfunctional isocyanate compound is 5 to 95 mol.

2. The encapsulation material for the energy storage device according to claim 1, wherein, The ratio of the number of isocyanate groups in the polyfunctional isocyanate compound to the number of hydroxyl groups in the polyester polyol resin is 2 to 60.

3. The encapsulation material for an energy storage device according to claim 1 or 2, wherein, The polyfunctional isocyanate compound further contains an adduct of toluene diisocyanate.

4. The encapsulation material for the energy storage device according to claim 3, wherein, The ratio of the number of isocyanate groups from the isocyanurate body of the isophorone diisocyanate to the number of isocyanate groups from the adduct of the toluene diisocyanate contained in the polyfunctional isocyanate compound is 0.05 to 20.

5. The encapsulation material for an energy storage device according to claim 1 or 2, wherein, The adhesive layer has a mass of 2.0–6.0 g / m² per unit area. 2 .

6. The encapsulation material for an energy storage device according to claim 1 or 2, wherein, An anti-corrosion treatment layer is provided on one or both sides of the barrier layer.

7. A packaging material for an energy storage device, characterized in that, It is composed of a laminate, which at least sequentially comprises a substrate layer, a first adhesive layer, a barrier layer, a second adhesive layer, and a sealant layer. The first adhesive layer contains a polyfunctional isocyanate compound. The polyfunctional isocyanate compound contains the isocyanurate form of isophorone diisocyanate. Based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the isocyanate group content of the isocyanurate body of the isophorone diisocyanate in the polyfunctional isocyanate compound is 25-75 mol%. When the substrate layer is removed to expose the first adhesive layer, and the attenuated total internal reflection of the exposed adhesive layer is measured using Fourier transform infrared spectroscopy from the outermost surface of the adhesive layer, the baseline transmittance T0 at 2100 cm⁻¹ is... -1 Up to 2400cm -1 The minimum transmittance T1 detected within the range, and at 1670 cm⁻¹ -1 Up to 1700cm -1 The minimum transmittance T2 detected within the range satisfies the relationship 0.06≤(T0-T1) / (T0-T2)≤0.

4.

8. The encapsulation material for an energy storage device according to claim 7, characterized in that, The first adhesive layer comprises a polyfunctional isocyanate compound, which is composed of at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing an aromatic ring in their molecular structure.

9. The encapsulation material for an energy storage device according to claim 8, characterized in that, The first adhesive layer contains a urethane resin, which is formed from at least one polyol selected from the group consisting of polyester polyols, acrylic polyols and polycarbonate diols, and the polyfunctional isocyanate compound.

10. The encapsulation material for an energy storage device according to claim 9, characterized in that, The ratio of the number of isocyanate groups in the polyfunctional isocyanate polymer to the number of hydroxyl groups in the polyol is 5 to 60.

11. The encapsulation material for an energy storage device according to claim 9, characterized in that, The coating weight of the urethane resin after drying is 2.0 g / m². 2 Above 6.0g / m 2 the following.

12. The encapsulation material for an energy storage device according to any one of claims 7 to 11, characterized in that, The barrier layer is aluminum foil.

13. The encapsulation material for an energy storage device according to any one of claims 7 to 11, characterized in that, The thickness of the barrier layer is 15–100 μm.

14. The encapsulation material for an energy storage device according to any one of claims 7 to 11, characterized in that, In the barrier layer, there is an anti-corrosion treatment layer between the first adhesive layer and the barrier layer, or between the second adhesive layer and the barrier layer, or both.

15. The encapsulation material for an energy storage device according to claim 1 or 7, characterized in that, The substrate layer is made of polyamide film or polyester film.

16. An encapsulation material for an energy storage device, wherein, It comprises at least a substrate layer, a barrier layer, and a sealant layer in sequence, characterized in that, An adhesive layer containing a polyurethane compound and a polyamide-imide resin is provided between the substrate layer and the barrier layer. In the adhesive layer, the solid content (A) of the polyamide-imide resin is 1.0% by mass < A < 20.0% by mass, relative to the solid content of the polyurethane compound. The number-average molecular weight (Mn) of the polyamide-imide resin is 3000 < Mn < 36000. The polyurethane compound is composed of the reaction product of at least one polyol resin and at least one polyfunctional isocyanate compound. The ratio (NCO / OH) of the amount of isocyanate in the polyfunctional isocyanate compound to the amount of hydroxyl groups in the polyol resin is 1.5 < NCO / OH < 40.

0.

17. The encapsulation material for an energy storage device according to claim 16, characterized in that, The polyol resin is at least one polyol resin selected from the group consisting of polyester polyol, acrylic polyol and polycarbonate polyol.

18. The encapsulation material for an energy storage device according to claim 16 or 17, characterized in that, The polyfunctional isocyanate compound is at least one isocyanate polymer selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing an aromatic ring in their molecular structure.

19. The encapsulation material for an energy storage device according to claim 16, characterized in that, The polyfunctional isocyanate compound contains the isocyanurate form of isophorone diisocyanate. Based on a total isocyanate group content of 100 mol% in the polyfunctional isocyanate compound, the content of isocyanate groups from the isocyanurate body of the isophorone diisocyanate in the polyfunctional isocyanate compound is 5 to 95 mol.

20. The packaging material according to any one of claims 1, 7, and 16, It is used in all-solid-state batteries.

21. An energy storage device, comprising: Energy storage device main body, Current output terminals extending from the main body of the energy storage device, and The encapsulation material for the energy storage device according to any one of claims 1 to 19, which clamps the current output terminal and houses the main body of the energy storage device.

Citation Information

Patent Citations

  • External facing material for power storage device

    JP2013101765A

  • Adhesive resin compositions, adhesives containing the same, adhesive sheets, and printed circuit boards containing adhesive sheets as adhesive layers.

    CN102264855A

  • Polyurethane adhesive for packaging materials for batteries, packaging material for batteries, battery container, and battery

    CN103975035A

  • Sheathing material for lithium batteries

    EP3116044A1

  • Exterior material for power storage device and method for manufacturing exterior material for power storage device

    EP3413371A1